Articles, systems and methods including articles having halogen reservoirs
Patent Information
- Application Number
- JP2023528232
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-12
- Filing Date
- 2021-11-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-11-12
Smart Images

Figure 0007634669000007 
Figure 0007634669000008 
Figure 0007634669000009
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 113,047, filed November 12, 2020, entitled “ARTICLES COMPRISING A PLURALITY HALOGEN RESERVOIRS, SYSTEMS AND METHODS INCLUDING THE SAME,” the entirety of which is incorporated herein by reference.
[0002] FIELD OF THE DISCLOSURE This disclosure relates to the field of pollution control systems and methods for removing compounds and particulate matter from gas streams. [Background technology]
[0003] Coal-fired power plants, municipal waste incinerators, and oil refineries generate large amounts of combustion exhaust gases, which contain a wide variety of significant amounts of environmental pollutants, such as sulfur oxides (SO 2 and S.O. 3 ), nitrogen oxides (NO, NO 2 ), mercury (Hg) vapor, and particulate matter (PM). In the United States, burning coal alone produces about 27 million tons of SO 2 , and 45 tons of Hg annually. Thus, there is a need for improved control systems and methods for removing sulfur oxides, mercury vapor, and particulate matter from industrial flue gases, such as coal-fired power plant flue gases. Summary of the Invention [Means for solving the problem]
[0004] In some embodiments, an improved and durable pollution control system is provided that can simultaneously remove a variety of flue gas pollutants. These pollutants include, but are not limited to, SO x, Hg vapor, and PM2.5 (particulate matter with a diameter of 2.5 micrometers or less). Some embodiments may include a simple pollution control system that does not generate secondary pollutants. In some embodiments, the pollution control system may provide the required amount of halogen source for an extended period of time. Specifically, the flue gas treatment device may include a more durable and longer lasting halogen source in combination with the sorbent polymer composite substrate. In some embodiments, the sorbent polymer composite substrate is not leached with solutions generated during the treatment process.
[0005] Some embodiments of the present disclosure relate to an article having a layered structure that may include a halogen source and an SPC. In some embodiments, the article described herein allows delayed release of at least one halogen source from a halogen reservoir. The halogen reservoir may form part of the article described herein.
[0006] In some embodiments, the article comprises a flue gas treatment device. In some embodiments, the article is a flue gas treatment device. In some embodiments, the article is part of a flue gas treatment device.
[0007] In some embodiments, the article includes a first SPC layer, a second SPC layer, and a halogen reservoir, the halogen reservoir being disposed between the first SPC layer and the second SPC layer.
[0008] In some embodiments, the article comprises, or further comprises, at least one permeation control material.
[0009] In some embodiments of the article, the at least one permeation control material is in the form of at least one permeation control layer disposed between the first SPC layer and the halogen reservoir, between the second SPC layer and the halogen reservoir, or both, i.e., in some embodiments of the article, the at least one permeation control layer is in the form of at least one permeation control layer disposed between the first SPC layer and the halogen reservoir and also between the second SPC layer and the halogen reservoir.
[0010] In some embodiments of the article, the at least one permeation control layer comprises a first layer of the at least one permeation control material, the first layer being disposed between the first SPC layer and the halogen reservoir, and a second layer of the at least one permeation control material, the second layer being disposed between the second SPC layer and the halogen reservoir.
[0011] In some embodiments, an article comprises a sorbent polymer composite (SPC) and a plurality of halogen reservoirs embedded within the SPC, each of the plurality of halogen reservoirs comprising 5 wt% to 95 wt% of at least one permeation control material, based on the average weight of each halogen reservoir, and 5 wt% to 50 wt% of at least one halogen source, based on the average weight of each halogen reservoir.
[0012] In some embodiments of the article, the SPC comprises a polymeric material.
[0013] In some embodiments of the article, the polymeric material comprises at least one of polyfluoroethylene propylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), terpolymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride (THV), polychlorofluoroethylene (PCFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyparaxylylene (PPX), polylactic acid (PLLA), polyethylene (PE), expanded polyethylene (ePE), polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), or any combination thereof.
[0014] In some embodiments of the article, the polymeric material comprises PVDF.
[0015] In some embodiments of the article, the PVDF is a PVDF homopolymer.
[0016] In some embodiments of the article, the PVDF is a PVDF copolymer.
[0017] In some embodiments of the article, the PVDF copolymer is a copolymer of PVDF and hexafluoropropylene (HFP).
[0018] In some embodiments of the article, the polymeric material comprises PTFE.
[0019] In some embodiments of the article, the polymeric material comprises ePTFE.
[0020] In some embodiments of the article, the polymeric material comprises fibrils and nodes, and the polymeric material becomes porous upon stretching such that voids form between the fibrils and nodes.
[0021] In some embodiments of the article, the at least one halogen source comprises at least a metal halide, an ammonium halide, an elemental halogen, or any combination thereof.
[0022] In some embodiments of the article, the at least one halogen source comprises at least sodium chloride, potassium chloride, sodium bromide, potassium bromide, sodium iodide, potassium iodide, or any combination thereof.
[0023] In some embodiments of the article, the at least one halogen source comprises at least an ammonium halide.
[0024] In some embodiments of the article, the at least one halogen source comprises at least tetramethylammonium iodide, tetrabutylammonium iodide, tetraethylammonium iodide, tetrapropylammonium iodide, tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium triiodide, tetrabutylammonium tribromide, tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, or any combination thereof.
[0025] In some embodiments of the article, the at least one halogen source comprises at least an elemental halogen.
[0026] In some embodiments of the article, the elemental halogen is elemental iodine (I 2 ), elemental chlorine (Cl 2 ), elemental bromine (Br 2 ) is at least one of the following.
[0027] In some embodiments of the article, the at least one halogen source comprises tetrabutylammonium iodide (TBAI).
[0028] In some embodiments of the article, the at least one halogen source comprises potassium iodide (KI).
[0029] In some embodiments of the article, the at least one halogen source comprises at least one phosphonium halide.
[0030] In some embodiments of the article, the at least one phosphonium halide is selected from the group consisting of tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI), and the like. 3 ), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof. In some embodiments, the at least one phosphonium halide is selected from the group consisting of tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI), and the like. 3 ), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof.
[0031] In some embodiments of the article, the at least one phosphonium halide is ETPPI.
[0032] In some embodiments of the article, the article comprises a plurality of halogen reservoirs in an amount sufficient to provide a release rate of total halogen from the article that does not exceed 0.5% of the total halogen in the article per day under conditions in which a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days, the flue gas stream having a temperature of at least 50° C. and a relative humidity of at least 95%, and the gas stream having at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of
[0033] In some embodiments of the article, the article comprises a plurality of halogen reservoirs in an amount sufficient to provide a release rate of total halogen from the article that does not exceed 2% of the total halogen in the article per day under conditions in which a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days, the flue gas stream having a temperature of at least 20° C. and a relative humidity of at least 95%, and the gas stream having at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of
[0034] In some embodiments of the article, at least one of the plurality of halogen reservoirs is in the form of an encapsulated bead, the encapsulated bead comprising a core, the at least one halogen source, the at least one halogen source being present on at least a surface of the core, and the permeation control material, the permeation control material encapsulating the core.
[0035] In some embodiments of the article, the core comprises activated carbon.
[0036] In some embodiments of the article, at least one of the plurality of halogen reservoirs is in the form of a reservoir particle, the reservoir particle comprising the permeation control material, the permeation control material being in the form of a permeation control particle, and the at least one halogen source, the at least one halogen source being present on at least a surface of the permeation control particle.
[0037] In some embodiments of the article, the permeation control material comprises polystyrene, cross-linked polystyrene-divinylbenzene (PS-DVB), or a combination thereof.
[0038] In some embodiments of the article, the reservoir particle further comprises a second permeation control material, the second permeation control material surrounding the at least one halogen source on a surface of the permeation control particle.
[0039] In some embodiments of the article, the plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, each of the reservoir clusters comprising the at least one halogen source and the permeation control material.
[0040] In some embodiments of the article, the plurality of reservoir clusters are in the form of a plurality of halogen reservoir strips embedded throughout the SPC.
[0041] In some embodiments of the article, the plurality of reservoir clusters are in the form of a plurality of halogen reservoir agglomerates mixed with SPC.
[0042] In some embodiments of the article, the sufficient amount of the plurality of halogen reservoirs is between 5% and 75% by weight of the plurality of halogen reservoirs based on the total weight of the article.
[0043] In some embodiments of the article, the sufficient amount of the plurality of halogen reservoirs is between 5% and 50% by weight of the plurality of halogen reservoirs based on the total weight of the article.
[0044] In some embodiments, the method includes obtaining a sorbent polymer composite (SPC) and obtaining a plurality of halogen reservoirs, each of the plurality of halogen reservoirs comprising 5 wt% to 95 wt% of at least one permeation control material, based on the average weight of each halogen reservoir, and 5 wt% to 50 wt% of at least one halogen source, based on the average weight of each halogen reservoir, and forming an article having the plurality of halogen reservoirs embedded within the SPC.
[0045] In some embodiments of the method, at least one of the plurality of halogen reservoirs is in the form of an encapsulated bead, and the method further includes forming the encapsulated bead by obtaining at least one particle forming a core, depositing the at least one halogen source onto a surface of the at least one particle, and encapsulating the core with the at least one permeation control material to form the encapsulated bead.
[0046] In some embodiments of the method, the at least one halogen source is deposited onto the surface of the at least one particle as a solution.
[0047] In some embodiments of the method, the at least one halogen source is deposited onto the surface of the at least one particle in a vapor phase.
[0048] In some embodiments of the method, the at least one particle is a carbon particle.
[0049] In some embodiments of the method, at least one of the plurality of halogen reservoirs is in the form of a reservoir particle, and the reservoir particle is formed by obtaining the at least one permeation control material in the form of a permeation control particle and depositing at least one halogen source onto a surface of the permeation control particle.
[0050] The method further includes, after depositing the at least one halogen source on a surface of the permeation control particle, depositing a second permeation control material onto at least a portion of the reservoir particle to form a second permeation control layer surrounding the at least one halogen source.
[0051] In some embodiments of the method, the plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, and the method further includes forming each of the plurality of reservoir clusters by mixing a plurality of particles with at least one halogen source and at least one permeation control material to form a mixture, forming the mixture into a film or portion, forming the film or portion into a halogen reservoir piece, and embedding the halogen reservoir piece into the SPC.
[0052] In some embodiments of the method, the plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, and the method further includes forming each of the plurality of reservoir clusters by obtaining an SPC agglomerate, mixing a plurality of particles with at least one halogen source and at least one permeation control material to form a reservoir agglomerate, and mixing the SPC agglomerate with the reservoir agglomerate to form the article.
[0053] In some embodiments, the method further comprises flowing a flue gas stream through contact with the article, wherein the flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%, and wherein the flue gas stream contains at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m based on the total volume of said flue gas stream. 3 and mercury vapor at a concentration of 0.5% or less, and the release rate of the total halogens in said article does not exceed 0.5% of the total halogens in said article per day. [Brief description of the drawings]
[0054] Some embodiments of the present disclosure will now be described, by way of example only, with reference to the accompanying drawings, in which: With specific reference now to the drawings in detail, it is emphasized that the illustrated embodiment is by way of example only and is for illustrative purposes only to discuss embodiments of the present disclosure. In this regard, the description taken together with the drawings will make apparent to those skilled in the art how to practice embodiments of the present disclosure.
[0055] [Figure 1A] FIG. 1A is a cross-sectional view of a non-limiting embodiment of a sorbent polymer composite (SPC) described herein.
[0056] [Figure 1B] FIG. 1B illustrates an additional non-limiting embodiment of a sorbent polymer composite (SPC) described herein.
[0057] [Diagram 2] 2A-2F depict non-limiting embodiments of a halogen reservoir encapsulated by a permeation control material incorporated into a sorbent polymer composite (SPC) according to some embodiments of the disclosure.
[0058] [Figure 3A] FIG. 3A is an electronic image showing a plurality of halogen reservoir particles in the form of coated iodine loaded particles according to some non-limiting embodiments of the disclosure.
[0059] [Figure 3B] FIG. 3B is an electronic image showing a sorbent polymer composite (SPC) including a plurality of reservoir particles in the form of coated iodine-loaded particles according to certain non-limiting embodiments of the disclosure.
[0060] [Figure 4] 4 and 4B are electronic images showing a sorbent polymer composite (SPC) having one or more halogen reservoir particles embedded therein, according to certain non-limiting embodiments of the disclosure.
[0061] [Figure 5A] FIG. 5A illustrates an encapsulated bead according to some non-limiting embodiments of the present disclosure.
[0062] [Figure 5B] FIG. 5B is an electronic image showing a collection of encapsulated beads according to some non-limiting embodiments of the disclosure.
[0063] [Figure 6] 6A and 6B are a series of photographs showing halogen reservoir clusters according to certain non-limiting embodiments of the disclosure.
[0064] [Figure 7] FIG. 7 is a graph showing the relative iodine content over time for several samples according to several non-limiting embodiments of the disclosure.
[0065] [Figure 8] FIG. 8 is a graph showing the relative iodine content over time for several samples according to several non-limiting embodiments of the disclosure.
[0066] [Figure 9] FIG. 9 is a graph showing relative iodine content versus time based on several comparative samples.
[0067] [Figure 10] FIG. 10 is a graph showing relative iodine content versus time based on several comparative samples.
[0068] [Figure 11] FIG. 11 illustrates a non-limiting embodiment of a pollution control system having any of the articles described herein.
[0069] [Figure 12] FIG. 12 illustrates a non-limiting embodiment of a flue gas flowing over a non-limiting embodiment of an article described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0070] Among the disclosed benefits and improvements, other objects and advantages of the present disclosure will become apparent from the following description taken in conjunction with the accompanying drawings. Detailed embodiments of the present disclosure are disclosed herein, but it should be understood that the disclosed embodiments are merely examples of the disclosed subject matter that may be embodied in various forms. In addition, each of the examples provided in connection with the various embodiments of the present disclosure are illustrative and not limiting.
[0071] Throughout the specification and claims, the following terms shall have the meanings explicitly associated therewith, unless the context clearly dictates otherwise. As used herein, the phrases "in one embodiment," "in an embodiment," and "in some embodiments" do not necessarily refer to the same embodiment, although they may. Additionally, as used herein, the phrases "in another embodiment" and "in some other embodiments" do not necessarily refer to different embodiments, although they may. It is intended that all embodiments of the present disclosure may be combined without departing from the scope or spirit of the present disclosure.
[0072] The term "between" as used herein does not necessarily mean that something is located immediately adjacent to another element. In general, the term refers to something being sandwiched between two or more other things. At the same time, the term "between" can also refer to something that is directly adjacent to two opposing things. Thus, in any one or more of the embodiments disclosed herein, a specific structural component that is located between two other structural elements is: It may be disposed directly between both of the two other structural elements, such that the particular structural component is in direct contact with both of the two other structural elements, or It may be disposed directly adjacent to only one of the two other structural elements, such that a particular structural component is in direct contact with only one of the two other structural elements, or It may be indirectly adjacent to only one of the two other structural elements, so that the particular structural component is not in direct contact with only one of the two other structural elements, and there is another element that juxtaposes the particular structural component with the one of the two other structural elements, or be indirectly adjacent to and between both of the two other structural elements, such that the particular structural component is not in direct contact with both of the two other structural elements and other features may be disposed therebetween; or Any combination of these may be arranged.
[0073] As used herein, the term "based on" is not exclusive and allows for based on additional unrecited factors, unless the context clearly dictates otherwise. Additionally, throughout the specification, the meanings of "a," "an," and "the" include plural references. The meaning of "in" includes "in" and "on."
[0074] All prior patents and publications cited herein are incorporated by reference in their entirety.
[0075] Sorbent polymer composites (SPCs) have been found to be particularly effective in removing undesirable components from flue gas streams. One such undesirable component is at least one SO x Chemical compounds and mercury vapor.
[0076] The use of at least one halogen source can increase the removal efficiency of SPC. However, in some cases, the at least one halogen source may not be durable enough to allow the SPC (and the system containing it, such as a fixed bed absorption system) to continue to operate for many years. In some cases, this occurs because the at least one halogen source may be released from the sorbent when added.
[0077] Thus, some embodiments of the present disclosure provide an exemplary solution in which multiple halogen reservoirs allow at least one halogen source to be released over time. The multiple halogen reservoirs allow the SPC (and systems including the same, e.g., fixed bed absorption systems) to operate (e.g., be in service) for longer periods of time compared to SPCs that do not include multiple halogen reservoirs.
[0078] As used herein, "sorbent" refers to a material that has the property of collecting molecules of another material by at least one of absorption, adsorption, or a combination thereof. The sorbent material of the sorbent polymer composite includes at least one of activated carbon, coal-derived carbon, lignite-derived carbon, wood-derived carbon, palm-derived carbon, silica gel, zeolite, or any combination thereof.
[0079] As used herein, the term "composite" refers to a material comprising two or more component materials having different physical or chemical properties, the combination of the two or more component materials resulting in a material having characteristics that differ from those of the individual components.
[0080] As used herein, a "sorbent polymer composite (SPC)" is a composite comprising a sorbent and a polymer. In embodiments, a sorbent polymer composite may include sorbent particles incorporated into the microstructure of a polymer.
[0081] The sorbent polymer composite material further comprises a halogen source. In some embodiments, the halogen source may be incorporated into the sorbent polymer composite material by any suitable technique, including, but not limited to, imbibing, impregnating, adsorbing, mixing, sprinkling, spraying, dipping, painting, coating, ion exchange, or otherwise applying the halogen source to the sorbent polymer composite. In some embodiments, the halogen source may be disposed within the sorbent polymer composite material, for example, within any pores of the sorbent polymer composite material. In some embodiments, the halogen source may be provided in a solution. The solution may be contacted in situ with the sorbent polymer composite material under system operating conditions. The halogen source of the sorbent polymer composite may be a halogen salt, an elemental halogen, or any combination thereof. In some embodiments, the halogen source is selected from at least one of sodium chloride, potassium chloride, sodium bromide, potassium bromide, sodium iodide, potassium iodide, tetramethylammonium iodide, tetrabutylammonium iodide, tetraethylammonium iodide, tetrapropylammonium iodide, tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, elemental iodine (I2), elemental chlorine (Cl2), elemental bromine (Br2), or any combination thereof. Additional examples of the sorbent polymer complexes described herein and the halogen sources described herein are described in U.S. Patent No. 9,827,551 (1368) to Hardwick et al. and U.S. Patent No. 7,442,352 to Lu et al., each of which is incorporated herein by reference in its entirety.
[0082] As used herein, the term "reservoir" refers to a reservoir that contains at least one material. The reservoir is configured to release at least one material over a period of time. In some non-limiting embodiments, the reservoir can include a permeation control material.
[0083] The term "halogen reservoir" as used herein means a reservoir containing at least one halogen source, wherein the at least one halogen source is configured to be released from storage over a predetermined period of time.
[0084] As used herein, "embedded" means that a first material is distributed throughout a second material.
[0085] As used herein, the term "permeation control material" refers to a material that is configured to release one or more substances from a reservoir at a slower rate than if the substances were released in the absence of a permeation control layer.
[0086] As used herein, the term "halogen source" refers to any compound that contains at least one halide ion or elemental halogen. The halogen source of the flue gas treatment device is selected from tetrabutylammonium iodide, tetrabutylammonium triiodide, tetrabutylammonium tribromide, or tetrabutylammonium bromide. In another embodiment, the halogen source is a compound having the formula N(R1R2R3R4)X, where N is nitrogen and X=I. - ,Br - ,I 3 - ,BrI 2 - ,Br 2 I - ,Br 3 -and R1, R2, R3, and R4 are selected from the group consisting of hydrocarbons having from about 1 to about 18 carbon atoms, which may be simple alkyls, including, for example, linear or branched alkyls. The halogen source may include a trihalide, which is formed from its halide precursor by acid treatment in the presence of an oxidizing agent. In a further embodiment, the halogen source is a trihalide, which is formed from its halide precursor by acid treatment in the presence of an oxidizing agent, which is selected from the group consisting of hydrogen peroxide, alkali metal persulfates, alkali metal monopersulfates, potassium iodate, potassium monopersulfate, oxygen, iron(III) salts, iron(III) nitrate, iron(III) sulfate, iron(III) oxide, and combinations thereof.
[0087] As used herein, the "average weight of each halogen reservoir" is calculated by adding up the weights of each of the halogen reservoirs in a particular article and then dividing the resulting sum of weights by the total weight of the article.
[0088] As used herein, the "total halogen release rate" is the release rate of the at least one halogen source from the article into the external environment in which the article resides. In some non-limiting embodiments, the external environment may be a combustion exhaust gas stream. In some embodiments, the at least one halogen source is released into the external environment exclusively from a sorbent polymer composite (SPC). In these embodiments, the "total halogen release rate" is the release rate from a sorbent polymer composite (SPC) into the external environment. In some embodiments, the at least one halogen source is released into the external environment exclusively from a plurality of halogen reservoirs. In these embodiments, the "total halogen release rate" is the release rate from a plurality of sorbent polymer composites (SPC) into the external environment. In some embodiments, the at least one halogen source is released into the external environment from a combination of a sorbent polymer composite (SPC) and a plurality of halogen reservoirs. In these embodiments, the "total halogen release rate" is a composite release rate that takes into account the release of the at least one halogen source from both the sorbent polymer composite (SPC) and the multiple halogen reservoirs. In some embodiments, the article comprises multiple halogen sources. In these embodiments, the "total halogen release rate" is a composite release rate that takes into account the release of all of the multiple halogen sources in the article. Determining the release rate is further described below.
[0089] The term "combustion exhaust gas stream" as used herein means a gaseous mixture comprising at least one by-product of a combustion process (e.g., a coal combustion process). In some embodiments, the flue gas stream may consist entirely of by-products of the combustion process. In some embodiments, the flue gas stream may comprise an elevated concentration of at least one gas relative to the concentration resulting from the combustion process. For example, in one non-limiting example, the flue gas stream may be subjected to a "scrubbing process". During the scrubbing process, water vapor may be added to the flue gas stream. Thus, in some such embodiments, the flue gas stream may comprise an elevated concentration of water vapor relative to the initial water vapor concentration resulting from the combustion. Similarly, in some embodiments, the flue gas stream may comprise a reduced concentration of at least one gas relative to the initial concentration of at least one gas output from the combustion process. This may occur, for example, by removing at least a portion of the at least one gas after combustion. In some embodiments, the flue gas stream may be in the form of a gaseous mixture that is a combination of by-products of multiple combustion processes.
[0090] As used herein, "SO x The term "sulfur compound" means any oxide of sulfur. x The compound may specifically refer to gaseous sulfur oxides, which are well-known environmental pollutants. x A non-limiting example of the compound is sulfur dioxide (SO 2 ) and sulfur trioxide (SO 3 ) included. x Additional non-limiting examples of compounds include sulfur monoxide (SO), disulfur monoxide (S 2 O), and disulfur dioxide (S 2 O 2 ).
[0091] As used herein, the term "mercury vapor" refers to gaseous compounds that contain mercury. Non-limiting examples of mercury vapor include elemental mercury vapor and oxidized mercury vapor.
[0092] As used herein, the term "oxidized mercury vapor" is defined as a vapor phase mercury compound that contains mercury in the positive valence state. Non-limiting examples of oxidized mercury vapor include mercurous halide and mercuric halide.
[0093] Various terms are used herein to describe the morphology of the halogen reservoir. These morphologies generally represent a local volume of material, i.e., a local volume of halogen or a local concentration of halogen. The terms encapsulated beads, particles, clusters, aggregates, and streaks all represent various morphologies of volumetrically localized halogen groups. As an example, beads can be approximately spherical and have a uniformly smooth outer surface or a non-uniformly smooth (i.e., bumpy) outer surface. Beads can be regular or irregular in shape or form. As another example, particles can have irregular shapes, sizes, or both. Particles and pieces are not uniformly spherical or have a generally uniformly smooth surface. Particles and pieces can be irregularly distributed inside something. In some embodiments, a particular morphology of volumetrically localized halogen can be described as being any one or more of these shapes.
[0094] The term "encapsulated bead" as used herein refers to a halogen reservoir in the form of a bead comprising a core and at least one encapsulant surrounding the core. At least one halogen source is present on at least the surface of the core. The core may comprise carbon, such as activated carbon. In some embodiments, the at least one encapsulant may comprise a permeation control material.
[0095] The term "reservoir particle" as used herein means a halogen reservoir in the form of a particle. In some embodiments, the "reservoir particle" may include at least one permeation control material as described herein and at least one halogen source. Some non-limiting examples of "reservoir particle" include some embodiments of reservoir pieces, reservoir aggregates, iodine-loaded beads, and encapsulated beads. At least one specific non-limiting example of a reservoir piece is detailed in Example 1. At least one specific non-limiting example of a reservoir aggregate is detailed in Example 1. At least one specific non-limiting example of an encapsulated bead is detailed in Example 2. At least one specific non-limiting example of an iodine-loaded bead is detailed in Example 3.
[0096] As used herein, the term "reservoir cluster" refers to a cluster of halogen reservoirs in the form of streaks or in the form of groups of irregular shapes.
[0097] As used herein, a "reservoir aggregate" is a collection or cluster of reservoir clusters. In some embodiments, each "reservoir aggregate" (i.e., each collection or cluster of reservoir clusters) may be localized within at least one specific SPC region.
[0098] As used herein, an "agglomerated mixture" refers to a mixture in which the components of the mixture are clustered together.
[0099] As used herein, "carbon particles" means any particles that contain carbon.
[0100] As used herein, "porous carbon particles" refers to carbon particles that have pores and does not include carbon particles that do not have pores, i.e., porous carbon particles exclude "non-porous" carbon particles.
[0101] As used herein, the term "permeation control particle" means at least one permeation control material in the form of a particle.
[0102] Some embodiments of the present disclosure relate to an article that includes a sorbent polymer composite (SPC) and a plurality of halogen reservoirs.
[0103] In some embodiments, the sorbent polymer composite (SPC) may comprise one or more homopolymers, copolymers, or terpolymers containing at least one fluoromonomer with or without additional non-fluorinated monomers.
[0104] In some embodiments, the polymeric material of the sorbent polymer composite (SPC) can include at least one of polyfluoroethylene propylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), terpolymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride (THV), polychlorofluoroethylene (PCFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyparaxylylene (PPX), polylactic acid (PLLA), polyethylene (PE), expanded polyethylene (ePE), polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), or any combination thereof.
[0105] In some embodiments, the polymeric material of the sorbent polymer composite (SPC) can include polyvinylidene fluoride (PVDF). In some embodiments, the PVDF can be a PVDF homopolymer. In some embodiments, the PVDF can be a PVDF copolymer. In some embodiments, the PVDF copolymer is a copolymer of PVDF and hexafluoropropylene (HFP). Non-limiting commercial examples of PVDF homopolymers or copolymers suitable for some embodiments of the present disclosure include, but are not limited to, Kynar Flex® and Kynar Superflex®, each commercially available from Arkema.
[0106] In some embodiments, the polymeric material of the sorbent polymer composite (SPC) can include polytetrafluoroethylene (PTFE). In some embodiments, the polymer is expanded polytetrafluoroethylene (ePTFE). In some embodiments, the structure of the polymer can become porous when stretched, such that voids can form between the fibrils and nodes of the polymer.
[0107] In some embodiments, the thickness of the sorbent polymer composite (SPC) is 0.2 mm to 2 mm, 0.4 mm to 2 mm, 0.8 mm to 2 mm, 1.2 mm to 2 mm, or 1.6 mm to 2 mm. In some embodiments, the thickness of the sorbent polymer composite (SPC) is 0.2 mm to 1.6 mm, 0.2 mm to 1.2 mm, 0.2 mm to 0.8 mm, or 0.2 mm to 0.4 mm. In some embodiments, the thickness of the sorbent polymer composite (SPC) is 0.4 mm to 1.6 mm, or 0.8 mm to 1.2 mm. In some embodiments, the thickness of the sorbent polymer composite (SPC) can be measured using cross-sectional scanning electron microscopy.
[0108] In some embodiments, the surface energy of the polymer of the sorbent polymer composite (SPC) is less than 31 dynes per cm, less than 30 dynes per cm, less than 25 dynes per cm, less than 20 dynes per cm, or less than 15 dynes per cm.
[0109] In some embodiments, the surface energy of the polymer of the sorbent polymer composite (SPC) is between 15 dynes per cm and 31 dynes per cm, between 20 dynes per cm and 31 dynes per cm, between 25 dynes per cm and 31 dynes per cm, between 30 dynes per cm and 31 dynes per cm, between 15 dynes per cm and 30 dynes per cm, between 15 dynes per cm and 25 dynes per cm, or between 15 dynes per cm and 20 dynes per cm.
[0110] In some embodiments, the surface energy of the polymer of the sorbent polymer composite (SPC) is between 20 dynes per cm and 25 dynes per cm.
[0111] In some embodiments, the SPC comprises a sorbent. In some embodiments, the sorbent of the SPC comprises activated carbon. In some embodiments, the sorbent comprises activated carbon derived from coal, lignite, wood, coconut shell, another carbonaceous material, or any combination thereof. In some embodiments, the sorbent can comprise silica gel, zeolite, or any combination thereof.
[0112] In some embodiments, the sorbent surface area of the sorbent polymer composite (SPC) is greater than or equal to 400 m 2 / g over 600m 2 / g over 800m 2 / g over 1000m 2 / g, 1200m 2 / g, 1400m 2 / g, 1600m 2 / g over 1800m 2 / g, or 2000m 2 / g.
[0113] In some embodiments, the sorbent surface area of the sorbent polymer composite (SPC) is greater than or equal to 400 m 2 / g~2000m 2 / g, 600m 2 / g~2000m 2 / g, 800m 2 / g~2000m 2 / g, 1000m 2 / g~2000m 2 / g, 1200m 2 / g~2000m 2 / g, 1400m 2 / g~2000m 2 / g, 1600m 2 / g~2000m 2 / g, or 1800m 2 / g~2000m 2 / g.
[0114] In some embodiments, the sorbent surface area of the sorbent polymer composite (SPC) is greater than or equal to 400 m 2 / g~1800m 2 / g, 400m 2 / g~1600m 2 / g, 400m 2 / g~1400m 2 / g, 400m 2 / g~1200m 2 / g, 400m 2 / g~1000m 2 / g, 400m 2 / g~800m 2 / g, or 400m 2 / g~600m 2 / g.
[0115] In some embodiments, the sorbent surface area of the sorbent polymer composite (SPC) is greater than or equal to 600 m 2 / g~1800m 2 / g, 800m 2 / g~1600m 2 / g, or 1000m 2 / g~1400m 2 / g.
[0116] In some embodiments, the at least one halogen source of the sorbent polymer composite (SPC) comprises a metal halide, an ammonium halide, an elemental halogen, or any combination thereof. In some embodiments, the at least one halogen source of the sorbent polymer composite (SPC) comprises a metal halide. In some embodiments, the at least one halogen source of the sorbent polymer composite (SPC) is selected from at least one of sodium chloride, potassium chloride, sodium bromide, potassium bromide, sodium iodide, or potassium iodide. In some embodiments, the at least one halogen source of the sorbent polymer composite (SPC) comprises an ammonium halide. In some embodiments, the at least one halogen source of the sorbent polymer complex (SPC) is selected from at least one of tetramethylammonium iodide, tetrabutylammonium iodide, tetraethylammonium iodide, tetrapropylammonium iodide, tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium triiodide, tetrabutylammonium tribromide, tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, or tetrabutylammonium chloride. In some embodiments, the at least one halogen source of the sorbent polymer complex (SPC) comprises an elemental halogen. In some embodiments, the at least one halogen source of the sorbent polymer complex (SPC) comprises elemental iodine (I 2 ), elemental chlorine (Cl 2 ), elemental bromine (Br 2 ) is selected from at least one of the following.
[0117] In some embodiments, the at least one halogen source of the sorbent polymer composite (SPC) is elemental iodine (I 2In some embodiments, the at least one halogen source of the sorbent polymer complex (SPC) is tetrabutylammonium iodide (TBAI). In some embodiments, the at least one halogen source of the sorbent polymer complex (SPC) is potassium iodide (KI).
[0118] In some embodiments, the at least one halogen source of the sorbent polymer composite (SPC) comprises at least one phosphonium halide.
[0119] In some embodiments, the at least one phosphonium halide is selected from the group consisting of tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI), and the like. 3 ), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof. In some embodiments, the at least one phosphonium halide is tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI 3 ), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof.
[0120] In some embodiments, the at least one phosphonium halide is selected from the group consisting of tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI), and the like. 3 In some embodiments, the at least one phosphonium halide is selected from the group consisting of tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPBr), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), or any combination thereof. 3), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), or any combination thereof.
[0121] In some embodiments, the at least one phosphonium halide is ethyltriphenylphosphonium iodide (ETPPI).
[0122] In some embodiments, the at least one halogen source may be incorporated into the sorbent polymer composite (SPC) by any suitable technique, including, but not limited to, imbibing, impregnating, adsorbing, mixing, sprinkling, spraying, dipping, painting, coating, ion exchange, or otherwise applying the at least one halogen source to the sorbent polymer composite (SPC). In some embodiments, the at least one halogen source may be disposed within the sorbent polymer composite (SPC), for example, within any pore of the sorbent polymer composite (SPC). In some embodiments, the at least one halogen source may be provided in a solution, which may be contacted in situ with the sorbent polymer composite (SPC) under system operating conditions.
[0123] 1A is a cross-sectional view of a non-limiting embodiment of a sorbent polymer composite (SPC) 100 described herein. In this non-limiting embodiment, the sorbent polymer composite (SPC) 100 includes a sorbent 102 partially or completely covering a polymer 101. In this non-limiting embodiment, at least one halogen source 103 (as described herein) can partially or completely cover a portion of the sorbent 102. In some embodiments, the at least one halogen source 103 can be imbibed into the pores of the sorbent 102.
[0124] 1B illustrates an additional non-limiting embodiment of a sorbent polymer composite (SPC) 100 described herein. As shown, the sorbent polymer composite (SPC) 100 can include sorbent particles 206. The sorbent particles 206 are embedded into a polymer microstructure 205. In some embodiments, the particles 206 can be activated carbon particles. In some embodiments, the polymer microstructure 205 can include fibrils. In some embodiments, the polymer can be expanded PTFE.
[0125] In some embodiments, each of the multiple halogen reservoirs is embedded within a sorbent polymer composite (SPC). Figures 2A-2F are simplified diagrams illustrating halogen reservoirs incorporated into a sorbent polymer composite (SPC) according to non-limiting embodiments of the present disclosure. In the non-limiting embodiments of Figures 2A-2F, article 200 may include a sorbent polymer composite (SPC) 201 and may further include multiple halogen reservoirs 202 embedded within sorbent polymer composite (SPC) 201. As further shown, multiple halogen reservoirs 202 may include at least one halogen source 203 and at least one permeation control material 204 as described herein. As further shown in Figures 2A-2F, multiple halogen reservoirs 202 may be in the form of multiple halogen reservoir clusters.
[0126] For example, as shown in the non-limiting embodiment depicted in FIG. 2A, the multiple halogen reservoirs 202 in the form of a multiple reservoir cluster may be in the form of a "rectangular reservoir piece" made of a halogen reservoir film or portion, e.g., as further described in Example 1. For example, as shown in the non-limiting embodiment depicted in FIG. 2B, the halogen reservoirs 202 in the form of a multiple reservoir cluster may be in the form of an "oval reservoir piece." For example, as shown in the non-limiting embodiment depicted in FIG. 2C, the halogen reservoirs 202 in the form of a plurality of reservoir clusters may be in the form of "irregular reservoir strips." For example, as shown in the non-limiting embodiment depicted in FIG. 2D, the halogen reservoirs 202 in the form of a plurality of reservoir clusters may be in the form of "nodular reservoir pieces."
[0127] As shown in the non-limiting embodiment depicted in Figure 2E, an article 200 according to some embodiments of the present disclosure may include an SPC 201. The SPC 201 may further include a plurality of halogen reservoirs 202 embedded within the SPC 201. As further shown, the plurality of halogen reservoirs 202 may include a mixture of at least one halogen source 203 and at least one permeation control material 204 as described herein. As further described, the plurality of halogen reservoirs 202 may be in the form of a plurality of reservoir clusters.
[0128] In some embodiments, reservoir clusters may merge to form streaks, as in the non-limiting example of FIG. 6B.
[0129] In some embodiments, the plurality of halogen reservoirs 202 in the form of a plurality of reservoir agglomerates may encompass the entire thickness of the article, as shown in the non-limiting embodiment of Figure 2E. In some embodiments, the thickness of the plurality of reservoir agglomerates may be equal to the thickness of the SPC 201.
[0130] As shown in the non-limiting embodiment depicted in FIG. 2F, the plurality of halogen reservoirs 202 in the form of a plurality of reservoir agglomerates may be in the form of a "circular reservoir particle."
[0131] In some embodiments, the reservoir cluster has at least one dimension between 0.1 mm and 100 mm. For example, in some embodiments, the at least one dimension may refer to a length, a width, a height, at least one radius, a circumference, an arc length, a contour length, or any combination thereof.
[0132] In some embodiments, the reservoir cluster has a dimension that is 0.1 mm in at least one dimension, 0.2 mm in at least one dimension, 0.3 mm in at least one dimension, 0.4 mm in at least one dimension, 0.5 mm in at least one dimension, 0.6 mm in at least one dimension, 0.7 mm in at least one dimension, 0.8 mm in at least one dimension, 0.9 mm in at least one dimension, 1 mm in at least one dimension, 5 mm in at least one dimension, 10 mm in at least one dimension, 15 mm in at least one dimension, 20 mm in at least one dimension, 25 mm in at least one dimension, 26 mm in at least one dimension, 27 mm in at least one dimension, 28 mm in at least one dimension, 29 mm in at least one dimension, 30 mm in at least one dimension, 31 mm in at least one dimension, 32 mm in at least one dimension, 33 mm in at least one dimension, 34 mm in at least one dimension, 35 mm in at least one dimension, 36 mm in at least one dimension, 37 mm in at least one dimension, 38 mm in at least one dimension, 39 mm in at least one dimension, 40 mm in at least one dimension, 41 mm in at least one dimension, 42 mm in at least one dimension, 43 mm in at least one dimension, 44 mm in at least one dimension, 45 mm in at least one dimension, 46 mm in at least one dimension, 47 mm in at least one dimension, 48 mm in at least one dimension, 49 mm in at least one dimension, 50 mm in at least one dimension, 50 mm in at least one dimension, 50 mm in at least one dimension, 50 mm in at least one dimension, 60 mm in at least one dimension, 62 mm in at least one dimension, 70 mm in at least one dimension, 72 mm in at least one dimension, 74 mm in at least one dimension, 76 mm in at least one dimension, 7 at least one dimension is 25 mm, at least one dimension is 30 mm, at least one dimension is 35 mm, at least one dimension is 40 mm, at least one dimension is 45 mm, at least one dimension is 50 mm, at least one dimension is 55 mm, at least one dimension is 60 mm, at least one dimension is 65 mm, at least one dimension is 70 mm, at least one dimension is 75 mm, at least one dimension is 80 mm, at least one dimension is 85 mm, at least one dimension is 90 mm, at least one dimension is 95 mm, or at least one dimension is 100 mm.
[0133] In some embodiments, the reservoir cluster has at least one dimension between 0.2 mm and 100 mm, 0.3 mm and 100 mm, 0.4 mm and 100 mm, 0.5 mm and 100 mm, 0.6 mm and 100 mm, 0.7 mm and 100 mm, 0.8 mm and 100 mm, 0.9 mm and 100 mm, 1 mm and 100 mm, 5 mm and 100 mm, 10 mm and 100 mm, 15 mm and 100 mm, 20 mm and 25 mm. 100mm, 25mm~100mm, 30mm~100mm, 35mm~100mm, 40mm~100mm, 45mm~100mm, 50mm~100mm, 55mm~100mm, 60mm~100mm, 65mm~100mm, 70mm~100mm, 75mm~100mm, 80mm~100mm, 85mm~100mm, 90mm~100mm, or 95mm~100mm.
[0134] In some embodiments, the reservoir cluster has at least one dimension between 0.1 mm and 95 mm, 0.1 mm and 90 mm, 0.1 mm and 85 mm, 0.1 mm and 80 mm, 0.1 mm and 75 mm, 0.1 mm and 70 mm, 0.1 mm and 65 mm, 0.1 mm and 60 mm, 0.1 mm and 55 mm, 0.1 mm and 50 mm, 0.1 mm and 45 mm, 0.1 mm and 40 mm, 0.1 mm and 35 mm, 0.1 mm and 30 mm, 0.1 mm and 25 mm, 0.1 mm and 20 mm, 0.1 mm and 15 mm, 0.1 mm and 10 mm, 0.1 mm and 5 mm, 0.1 mm and 1 mm. In some embodiments, at least one dimension is between 0.1 mm and 0.9 mm, between 0.1 mm and 0.8 mm, between 0.1 mm and 0.7 mm, between 0.1 mm and 0.6 mm, between 0.1 mm and 0.5 mm, between 0.1 mm and 0.4 mm, between 0.1 mm and 0.3 mm, or between 0.1 mm and 0.2 mm.
[0135] In some embodiments, each halogen reservoir of the plurality of halogen reservoirs comprises at least one permeation control material. In some embodiments, the permeation control material comprises polycarbonate (PC), ethyl cellulose (EC), polystyrene (PS), polystyrene-divinylbenzene (PS-DVB), at least one polyolefin, at least one polyvinylidene fluoride (PVDF) homopolymer or copolymer, or any combination thereof.
[0136] In some embodiments, the PVDF copolymer is a copolymer of PVDF and hexafluoropropylene (HFP). Non-limiting commercial examples of PVDF homopolymers or copolymers suitable for some embodiments of the present disclosure include, but are not limited to, Kynar Flex® and Kynar Superflex®, each commercially available from Arkema.
[0137] In some embodiments, the permeation control material comprises a polyethylene wax.In some embodiments, the permeation control material comprises a polypropylene wax.
[0138] In some embodiments, each halogen reservoir of the plurality of halogen reservoirs comprises between 5 wt% and 95 wt% of at least one permeation control material, based on the average weight of each halogen reservoir.
[0139] In some embodiments, each halogen reservoir of the plurality of halogen reservoirs comprises 5 wt% of at least one permeation control material, based on the average weight of each halogen reservoir. In some embodiments, each halogen reservoir of the plurality of halogen reservoirs comprises 10 wt% of at least one permeation control material, 15 wt% of at least one permeation control material, 20 wt% of at least one permeation control material, 25 wt% of at least one permeation control material, 30 wt% of at least one permeation control material, 35 wt% of at least one permeation control material, 40 wt% of at least one permeation control material, 45 wt% of at least one permeation control material, based on the average weight of each halogen reservoir. The permeation control material may comprise 50 wt% of at least one permeation control material, 55 wt% of at least one permeation control material, 60 wt% of at least one permeation control material, 65 wt% of at least one permeation control material, 70 wt% of at least one permeation control material, 75 wt% of at least one permeation control material, 80 wt% of at least one permeation control material, 85 wt% of at least one permeation control material, 90 wt% of at least one permeation control material, or 95 wt% of at least one permeation control material.
[0140] In some embodiments, each halogen reservoir of the plurality of halogen reservoirs comprises, based on the average weight of each halogen reservoir, 10 wt% to 95 wt% of at least one permeation control material, 15 wt% to 95 wt% of at least one permeation control material, 20 wt% to 95 wt% of at least one permeation control material, 25 wt% to 95 wt% of at least one permeation control material, 30 wt% to 95 wt% of at least one permeation control material, 35 wt% to 95 wt% of at least one permeation control material, 40 wt% to 95 wt% of at least one permeation control material, 45 wt% to 95 wt% of at least one permeation control material, or 50 wt% to 95 wt% of at least one permeation control material, based on the average weight of each halogen reservoir. at least one type of permeability control material, 50 wt% to 95 wt% of at least one type of permeability control material, 55 wt% to 95 wt% of at least one type of permeability control material, 60 wt% to 95 wt% of at least one type of permeability control material, 65 wt% to 95 wt% of at least one type of permeability control material, 70 wt% to 95 wt% of at least one type of permeability control material, 75 wt% to 95 wt% of at least one type of permeability control material, 80 wt% to 95 wt% of at least one type of permeability control material, 85 wt% to 95 wt% of at least one type of permeability control material, or 90 wt% to 95 wt% of at least one type of permeability control material.
[0141] In some embodiments, each halogen reservoir of the plurality of halogen reservoirs contains, based on the average weight of each halogen reservoir, 5 wt% to 10 wt% of at least one permeation control material, 5 wt% to 15 wt% of at least one permeation control material, 5 wt% to 20 wt% of at least one permeation control material, 5 wt% to 25 wt% of at least one permeation control material, 5 wt% to 30 wt% of at least one permeation control material, 5 wt% to 35 wt% of at least one permeation control material, 5 wt% to 40 wt% of at least one permeation control material, 5 wt% to 45 wt% of at least one permeation control material, or 5 wt% to 50 wt% of at least one permeation control material. at least one permeation control material, 5 wt% to 50 wt% of at least one permeation control material, 5 wt% to 55 wt% of at least one permeation control material, 5 wt% to 60 wt% of at least one permeation control material, 5 wt% to 65 wt% of at least one permeation control material, 5 wt% to 70 wt% of at least one permeation control material, 5 wt% to 75 wt% of at least one permeation control material, 5 wt% to 80 wt% of at least one permeation control material, 5 wt% to 85 wt% of at least one permeation control material, or 5 wt% to 90 wt% of at least one permeation control material.
[0142] In some embodiments, each of the plurality of halogen reservoirs comprises at least one halogen source, based on the average weight of each of the halogen reservoirs. In some embodiments, each of the plurality of halogen reservoirs comprises between 5 wt% and 50 wt% of the at least one halogen source, based on the average weight of each of the halogen reservoirs.
[0143] In some embodiments, each halogen reservoir of the plurality of halogen reservoirs comprises 5 wt% of at least one halogen source, 10 wt% of at least one halogen source, 15 wt% of at least one halogen source, 20 wt% of at least one halogen source, 25 wt% of at least one halogen source, 30 wt% of at least one halogen source, 35 wt% of at least one halogen source, 40 wt% of at least one halogen source, 45 wt% of at least one halogen source, or 50 wt% of at least one halogen source, based on the average weight of each halogen reservoir.
[0144] In some embodiments, each of the plurality of halogen reservoirs comprises between 10 wt% and 50 wt% of at least one halogen source, based on the average weight of each of the halogen reservoirs. In some embodiments, each of the plurality of halogen reservoirs comprises between 15 wt% and 50 wt%, between 20 wt% and 50 wt%, between 25 wt% and 50 wt%, between 30 wt% and 50 wt%, between 35 wt% and 50 wt%, between 40 wt% and 50 wt%, or between 45 wt% and 50 wt% of at least one halogen source, based on the average weight of each of the halogen reservoirs.
[0145] In some embodiments, each of the plurality of halogen reservoirs comprises between 5 wt% and 45 wt% of at least one halogen source, based on the average weight of each of the halogen reservoirs. In some embodiments, each of the plurality of halogen reservoirs comprises between 5 wt% and 40 wt% of at least one halogen source, between 5 wt% and 35 wt% of at least one halogen source, between 5 wt% and 30 wt% of at least one halogen source, between 5 wt% and 25 wt% of at least one halogen source, between 5 wt% and 20 wt% of at least one halogen source, between 5 wt% and 15 wt% of at least one halogen source, or between 5 wt% and 10 wt% of at least one halogen source, based on the average weight of each of the halogen reservoirs.
[0146] In some embodiments, the at least one halogen source of the multiple halogen reservoirs may be any halogen source described herein. In some embodiments, the at least one halogen source of the multiple halogen reservoirs is the same as the at least one halogen source of the sorbent polymer composite (SPC). In some embodiments, the at least one halogen source of the multiple halogen reservoirs is different from the at least one halogen source of the sorbent polymer composite (SPC).
[0147] In some embodiments, the article comprises a plurality of halogen reservoirs in an amount sufficient to result in a release rate of total halogen from the article that does not exceed a specified amount of total halogen in the article per day under conditions in which a combustion exhaust gas stream is flowed over at least one surface of the article for a period of at least 90 days.
[0148] As described herein, % per day refers to the amount of halogen relative to the total halogen content present at that time (not relative to the initial content), not relative to the weight of the SPC. In some embodiments, as further discussed herein, the decrease in iodine content (or release rate) is exponential (i.e., the decrease can be described as an exponential decay), as shown, for example, in Figures 7-10A. Thus, a constant "k" can be used to describe this behavior. "k" can be referred to as the "release rate constant", "decay constant", or "exponential decay constant".
[0149] In some embodiments, the release rate of total halogens from the article when a flue gas stream flows over at least one surface of the article for a period of at least 90 days is not more than 0.1% of the total halogens per day, not more than 0.2% of the total halogens per day, not more than 0.3% of the total halogens per day, not more than 0.4% of the total halogens per day, not more than 0.5% of the total halogens per day, not more than 0.6% of the total halogens per day, not more than 0.7% of the total halogens per day, not more than 0.8% of the total halogens per day, not more than 0.9% of the total halogens per day, not more than 1% of the total halogens per day, not more than 1.5% of the total halogens per day, not more than 2% of the total halogens per day, not more than 2.5% of the total halogens per day, not more than 3% of the total halogens per day, not more than 4% of the total halogens per day, not more than 5% of the total halogens per day.
[0150] In some embodiments, the release rate of the total halogen from the article is 0.1-2% of the total halogen per day when a flue gas stream flows over at least one surface of the article for a period of at least 90 days. In some embodiments, the release rate of the total halogen from the article is 0.2%-2% of the total halogen per day, 0.3%-2% of the total halogen per day, 0.4%-2% of the total halogen per day, 0.5%-2% of the total halogen per day, 0.6%-2% of the total halogen per day, 0.7%-2% of the total halogen per day, 0.8%-1% of the total halogen per day, 0.9%-2% of the total halogen per day, 1%-2% of the total halogen per day, or 1.5%-2% of the total halogen per day when a flue gas stream flows over at least one surface of the article for a period of at least 90 days.
[0151] In some embodiments, the release rate of the total halogen from the article is between 0.1% and 1.5% of the total halogen per day when a flue gas stream is passed over at least one surface of the article for a period of at least 90 days. In some embodiments, the release rate of the total halogen from the article is between 0.1% and 1% of the total halogen per day, between 0.1% and 0.9% of the total halogen per day, between 0.1% and 0.8% of the total halogen per day, between 0.1% and 0.7% of the total halogen per day, between 0.1% and 0.6% of the total halogen per day, between 0.1% and 0.5% of the total halogen per day, between 0.1% and 0.4% of the total halogen per day, between 0.1% and 0.3% of the total halogen per day, between 0.1% and 0.2% of the total halogen per day when a flue gas stream is passed over at least one surface of the article for a period of at least 90 days.
[0152] In some embodiments, the release rate of the total halogen from the article is between 0.2% and 0.9% of the total halogen per day when a flue gas stream is passed over at least one surface of the article for a period of at least 90 days. In some embodiments, the release rate of the total halogen from the article is between 0.3% and 0.8% of the total halogen per day, between 0.4% and 0.7% of the total halogen per day, or between 0.5% and 0.6% of the total halogen per day when a flue gas stream is passed over at least one surface of the article for a period of at least 90 days.
[0153] In some embodiments, the gas stream has a temperature of at least 20° C. and a relative humidity of at least 95%. In some embodiments, the gas stream contains at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of
[0154] In some embodiments, the gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%. In some embodiments, the gas stream contains at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of
[0155] In some embodiments, the temperature of the flue gas stream is greater than 20°C, greater than 30°C, greater than 40°C, greater than 50°C, greater than 60°C, greater than 60°C, greater than 70°C, greater than 75°C, greater than 80°C, greater than 85°C, or greater than 90°C.
[0156] In some embodiments, the temperature of the flue gas stream is less than 20°C, less than 30°C, less than 40°C, less than 50°C, less than 60°C, less than 70°C, less than 75°C, less than 80°C, 85°C, or less than 90°C.
[0157] In some embodiments, the temperature of the flue gas stream is between 20°C and 80°C, between 30°C and 80°C, between 40°C and 80°C, between 50°C and 80°C, between 60°C and 80°C, or between 70°C and 80°C.
[0158] In some embodiments, the temperature of the flue gas stream is between 20°C and 70°C, between 20°C and 60°C, between 20°C and 50°C, between 20°C and 40°C, or between 20°C and 30°C.
[0159] In some embodiments, the temperature of the flue gas stream is between 30°C and 70°C, or between 40°C and 60°C.
[0160] In some embodiments, the temperature of the flue gas stream is between 50°C and 70°C, between 60°C and 70°C, between 55°C and 70°C, or between 55°C and 60°C.
[0161] In some embodiments, the temperature of the flue gas stream is between 65°C and 70°C, between 70°C and 75°C, between 75°C and 80°C, between 80°C and 85°C, or between 85°C and 90°C.
[0162] In some embodiments, the temperature of the flue gas stream is between 65°C and 90°C, between 70°C and 90°C, between 75°C and 90°C, between 80°C and 90°C, or between 85°C and 90°C.
[0163] In some embodiments, the temperature of the flue gas stream is between 65°C and 75°C, between 65°C and 80°C, between 65°C and 85°C, or between 65°C and 90°C.
[0164] In some embodiments, the relative humidity of the flue gas stream is at least 95%. In some embodiments, the relative humidity of the flue gas stream is at least 96%, at least 97%, at least 98%, or at least 99%. In some embodiments, the relative humidity of the flue gas stream is 100%.
[0165] In some embodiments, the relative humidity of the flue gas stream is between 95% and 100%. In some embodiments, the relative humidity of the flue gas stream is between 96% and 100%, between 97% and 100%, between 98% and 100%, or between 99% and 100%.
[0166] In some embodiments, the relative humidity of the flue gas stream is between 95% and 96%, between 95% and 97%, between 95% and 98%, between 95% and 99%, or between 95% and 100%.
[0167] In some embodiments, the flue gas stream comprises at least one SO x In some embodiments, the combustion exhaust gas stream is free of at least one SO 2 compound at a concentration of at least 1 ppm, at least 5 ppm, at least 10 ppm, at least 20 ppm, at least 25 ppm, at least 30 ppm, at least 35 ppm, at least 40 ppm, at least 45 ppm, at least 50 ppm, at least 100 ppm, at least 500 ppm, or at least 1000 ppm. x Contains compounds.
[0168] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of at least 1 ppm to 200 ppm, 5 ppm to 200 ppm, 10 ppm to 200 ppm, 50 ppm to 200 ppm, or 100 ppm to 200 ppm. x Contains compounds.
[0169] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of between 20 ppm and 100 ppm, between 25 ppm and 100 ppm, between 30 ppm and 100 ppm, between 35 ppm and 100 ppm, between 40 ppm and 100 ppm, between 45 ppm and 100 ppm, between 50 ppm and 100 ppm, between 55 ppm and 100 ppm, between 60 ppm and 100 ppm, between 65 ppm and 100 ppm, between 70 ppm and 100 ppm, between 75 ppm and 100 ppm, between 80 ppm and 100 ppm, between 85 ppm and 100 ppm, between 90 ppm and 100 ppm, or between 95 ppm and 100 ppm. x Contains compounds.
[0170] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of from 20 ppm to 25 ppm, from 20 ppm to 30 ppm, from 20 ppm to 35 ppm, from 20 ppm to 40 ppm, from 20 ppm to 45 ppm, from 20 ppm to 50 ppm, from 20 ppm to 55 ppm, from 20 ppm to 60 ppm, from 20 ppm to 65 ppm, from 20 ppm to 70 ppm, from 20 ppm to 75 ppm, from 20 ppm to 80 ppm, from 20 ppm to 85 ppm, from 20 ppm to 90 ppm, from 20 ppm to 95 ppm, or from 20 ppm to 100 ppm. x Contains compounds.
[0171] In some embodiments, the combustion exhaust gas stream contains at least one SO at a concentration of from 1 ppm to 90 ppm, from 1 ppm to 80 ppm, from 1 ppm to 70 ppm, from 1 ppm to 90 ppm, from 1 ppm to 90 ppm, from 1 ppm to 60 ppm, from 1 ppm to 50 ppm, from 1 ppm to 40 ppm, from 1 ppm to 30 ppm, from 1 ppm to 20 ppm, from 1 ppm to 10 ppm, or from 1 ppm to 5 ppm. x Contains compounds.
[0172] In some embodiments, the flue gas stream is free of mercury vapor. ... 3 , at least 2 μg / m of the flue gas stream 3 , at least 3 μg / m of the flue gas stream 3 , at least 4 μg / m of the flue gas stream 3 , at least 5 μg / m of the flue gas stream 3 , at least 6 μg / m of the flue gas stream 3 , at least 7 μg / m of the flue gas stream 3 , at least 8 μg / m of the flue gas stream 3 , at least 9 μg / m of the flue gas stream 3 , at least 10 μg / m of the flue gas stream 3 , at least 15 μg / m of the flue gas stream 3 , at least 20 μg / m of the flue gas stream 3 or at least 50 μg / m of the flue gas stream 3 Contains mercury vapor at a concentration of.
[0173] In some embodiments, the flue gas stream has a concentration of at least 1 μg / m of the flue gas stream. 3 ~50μg / m 3 In some embodiments, the flue gas stream contains mercury vapor at a concentration of 5 μg / m of the flue gas stream. 3 ~50μg / m 3 , 10 μg / m of flue gas stream 3 ~50μg / m 3 , 20 μg / m of flue gas stream 3 ~50μg / m 3 or 40 μg / m of the flue gas stream. 3 ~50μg / m 3 Contains mercury vapor at a concentration of.
[0174] In some embodiments, the flue gas stream has a concentration of at least 1 μg / m of the flue gas stream. 3 ~10μg / m 3 In some embodiments, the flue gas stream contains mercury vapor at a concentration of 2 μg / m of the flue gas stream. 3 ~10μg / m 3 , 3 μg / m of flue gas stream 3 ~10μg / m 3 , 4 μg / m of flue gas stream 3 ~10μg / m 3 , 5 μg / m of flue gas stream 3 ~10μg / m 3 , 6 μg / m of flue gas stream 3 ~10μg / m 3 , 7 μg / m of flue gas stream 3 ~10μg / m 3 , 8 μg / m of flue gas stream 3 ~10μg / m 3 , 9 μg / m of flue gas stream 3 ~10μg / m 3 Contains mercury vapor at a concentration of.
[0175] In some embodiments, the flue gas stream has a concentration of at least 1 μg / m of the flue gas stream. 3 ~2μg / m 3 , 1 μg / m of flue gas stream 3 ~3μg / m 3 , 1 μg / m of flue gas stream3 ~4μg / m 3 , 1 μg / m of flue gas stream 3 ~5μg / m 3 , 1 μg / m of flue gas stream 3 ~6μg / m 3 , 1 μg / m of flue gas stream 3 ~7μg / m 3 , 1 μg / m of flue gas stream 3 ~8μg / m 3 or 1 μg / m of the flue gas stream. 3 ~9μg / m 3 Contains mercury vapor at a concentration of.
[0176] In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of at least 100 days. In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of at least 200 days, at least 300 days, at least 400 days, at least 500 days, at least 600 days, at least 700 days, at least 800 days, at least 900 days, at least 1,000 days, at least 2,000 days, at least 3,000 days, at least 4,000 days, or at least 5,000 days.
[0177] In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of between 100 days and 10,000 days, hi some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of between 500 days and 10,000 days, between 1,000 days and 10,000 days, or between 5,000 days and 10,000 days.
[0178] In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of from 100 days to 5,000 days, for a period of from 100 days to 1,000 days, or for a period of from 100 days to 500 days.
[0179] In some embodiments, the flue gas stream is flowed over at least one surface of the article for a period of from 500 days to 10,000 days, or from 1,000 days to 5,000 days.
[0180] In some embodiments, at least one of the plurality of halogen reservoirs is in the form of a reservoir particle, the reservoir particle comprising a first permeation control material and at least one halogen source, the first permeation control material is in the form of a permeation control particle, and the at least one halogen source is present on at least a surface of the permeation control particle.
[0181] In some embodiments, the reservoir particle further comprises a second permeation control material, the second permeation control material surrounding the at least one halogen source on the surface of the permeation control particle. In some embodiments, the first permeation control material and the second permeation control material comprise the same material. In some embodiments, the first permeation control material and the second permeation control material comprise different materials.
[0182] In some embodiments, the multiple halogen reservoirs are in the form of multiple reservoir clusters, each reservoir cluster containing a mixture of at least one halogen source and a permeation control material.
[0183] Figure 3A is an electronic image showing a collection 302 of halogen reservoir particles 301 according to certain non-limiting embodiments of the disclosure. Figure 3B is an electronic image showing a cross-section of a sorbent polymer composite (SPC) 303 containing the halogen reservoir particles of Figure 3A. A halogen reservoir particle 305 is embedded within the sorbent polymer composite (SPC) 303 along with a permeation control material 304 according to certain non-limiting embodiments of the disclosure.
[0184] FIG. 4A is a magnified electronic image of an article 400 showing a cross-section of a sorbent polymer composite (SPC) 430 including one halogen reservoir 410 in the form of a halogen reservoir particle embedded within the SPC 430 according to some non-limiting embodiments of the disclosure.
[0185] FIG. 4B is a magnified electronic image of one embodiment of article 400 showing a cross section of a halogen reservoir-containing sorbent polymer composite (SPC) 430 that includes reservoir particles 410 embedded within the SPC 430 .
[0186] In some embodiments, at least one of the plurality of halogen reservoirs is in the form of an encapsulated bead, the encapsulated bead comprising a core, hi some embodiments, the at least one halogen source is present on at least a surface of the core, and the permeation control material encapsulates the core forming the encapsulated bead.
[0187] The core may comprise any material, for example, in some embodiments, the core may comprise carbon, coal, lignite, wood, coconut shell, activated carbon derived from another carbonaceous material, silica gel, zeolite, or any combination thereof.
[0188] In some embodiments, the core comprises at least one carbon particle. In some embodiments, the at least one carbon particle may comprise any type of carbon particle listed herein. In some embodiments, the core comprises at least one carbon particle or a plurality of carbon particles.
[0189] In some embodiments, the at least one carbon particle or particles comprise activated carbon, hi some embodiments, the activated carbon is incorporated within the encapsulation bead in an amount between 25% and 50% by weight of the encapsulation bead.
[0190] In some embodiments, the activated carbon incorporated within the encapsulated beads is present in an amount of 25 wt% of the encapsulated beads, 30 wt% of the encapsulated beads, 35 wt% of the encapsulated beads, 40 wt% of the encapsulated beads, 45 wt% of the encapsulated beads, or 50 wt% of the encapsulated beads.
[0191] In some embodiments, the activated carbon incorporated within the encapsulated beads is present in an amount between 25 wt% and 30 wt%, between 25 wt% and 35 wt%, between 25 wt% and 40 wt%, between 25 wt% and 45 wt% of the encapsulated beads.
[0192] In some embodiments, the activated carbon incorporated within the encapsulated beads is present in an amount between 30 wt% and 50 wt%, between 35 wt% and 50 wt%, between 40 wt% and 50 wt%, between 45 wt% and 50 wt% of the encapsulated beads.
[0193] In some embodiments, the encapsulating bead comprises at least one permeation control material, hi some embodiments, the permeation control material of the encapsulating bead comprises at least one polyvinylidene (PVDF) homopolymer or copolymer, at least one polyolefin, polycarbonate (PC), polystyrene (PS), ethyl cellulose (EC), or any combination thereof.
[0194] In some embodiments, the permeation control material of the encapsulation beads comprises a polyethylene wax.In some embodiments, the permeation control material of the encapsulation beads comprises a polypropylene wax.
[0195] In some embodiments, the encapsulated beads comprise at least one halogen source, said at least one halogen source being present at least on a surface of at least one carbon particle.
[0196] In some embodiments, the size range of the encapsulated beads is 20 microns to 500 microns. In some embodiments, the release rate of the halogen increases with decreasing size of the encapsulated beads. In some embodiments, the size range of the encapsulated beads is 25 microns to 50 microns.
[0197] In some embodiments, the encapsulated beads include 20 micron sizes, 25 micron sizes, 30 micron sizes, 35 micron sizes, 40 micron sizes, 45 micron sizes, 50 micron sizes, 100 micron sizes, 150 micron sizes, 200 micron sizes, 250 micron sizes, 300 micron sizes, 350 micron sizes, 400 micron sizes, 450 micron sizes, and 500 micron sizes.
[0198] In some embodiments, the encapsulated beads include a size range of 20 microns to 25 microns, a size range of 20 microns to 25 microns, a size range of 20 microns to 30 microns, a size range of 20 microns to 35 microns, a size range of 20 microns to 40 microns, a size range of 20 microns to 45 microns, a size range of 20 microns to 50 microns, a size range of 20 microns to 100 microns, a size range of 20 microns to 150 microns, a size range of 20 microns to 200 microns, a size range of 20 microns to 250 microns, a size range of 20 microns to 300 microns, a size range of 20 microns to 350 microns, a size range of 20 microns to 400 microns, a size range of 20 microns to 450 microns, a size range of 20 microns to 500 microns.
[0199] In some embodiments, the size range of the encapsulated beads is 25 microns to 500 microns. In some embodiments, the size range of the encapsulated beads is 35 microns to 500 microns, 40 microns to 500 microns, 45 microns to 500 microns, 50 microns to 500 microns, 100 microns to 500 microns, 150 microns to 500 microns, 200 microns to 500 microns, 250 microns to 500 microns, 300 microns to 500 microns, 350 microns to 500 microns, 400 microns to 500 microns, or 450 microns to 500 microns.
[0200] In some embodiments, the encapsulated beads may be prepared by any method known to one of skill in the art, hi some embodiments, the encapsulated beads may be prepared by spray drying, spraying, spray congealing, coextrusion, coating, or coacervation.
[0201] In some embodiments, the encapsulated beads may be prepared by spray drying. In some embodiments, the spray drying process includes suspending carbon particles in a solution of a halogen source and a permeation control material, aerosolizing the suspension through a spray nozzle, evaporating the solvent, thereby producing encapsulated beads, and collecting the encapsulated bead population. In some embodiments, the at least one halogen source may be dissolved in a solution or pre-adsorbed on activated carbon.
[0202] In some embodiments, the solvent used for spray drying can be any low boiling point solvent.
[0203] In some embodiments, the boiling point of the solvent used for spray drying may be less than 100° C. In some embodiments, the boiling point of the solvent used for spray drying may be less than 75° C. In some embodiments, the boiling point of the solvent used for spray drying may be less than 50° C.
[0204] In some embodiments, the boiling point of the solvent used for spray drying may be between 50° C. and 100° C. In some embodiments, the boiling point of the solvent used for spray drying may be between 75° C. and 100° C. In some embodiments, the boiling point of the solvent used for spray drying may be between 50° C. and 75° C.
[0205] In some embodiments, the solvent used for spray drying can be any solvent that has the necessary solubility for the desired permeation control material.
[0206] In some embodiments, the solvent used for spray drying can be any solvent that has a solubility of at least 5 wt% for the desired permeation control material, hi some embodiments, the solvent used for spray drying can be any solvent that has a solubility of at least 25 wt%, at least 50 wt%, or at least 75 wt% for the desired permeation control material.
[0207] In some embodiments, the solvent used for spray drying can be any solvent that is non-reactive towards at least one halogen source.
[0208] In some embodiments, the solvent may be methylene chloride (DCM), tetrahydrofuran (THF), ethyl acetate (EtOAc), acetone, toluene, or any combination thereof.
[0209] In some embodiments, the encapsulated beads may be prepared using spray congealing. In some embodiments, the at least one halogen source may be pre-adsorbed onto carbon particles. In some embodiments, the carbon particles are activated carbon. In some embodiments, the at least one halogen source pre-adsorbed onto the carbon particles can be mixed into molten wax, aerosolized through a nozzle, solidified upon cooling, and then the encapsulated beads can be collected.
[0210] In some embodiments, the encapsulated beads may be incorporated into a sorbent polymer composite (SPC) using any process employed for the manufacture of SPC.
[0211] In some embodiments, the encapsulated bead content in the sorbent polymer composite (SPC) comprises 5 wt%, 10 wt%, 20 wt%, or 25 wt%.
[0212] In some embodiments, the encapsulated bead content in the sorbent polymer composite (SPC) includes a range of 10 wt% to 30 wt%. In some embodiments, the encapsulated bead content in the sorbent polymer composite (SPC) includes a range of 15 wt% to 30 wt%, 20 wt% to 30 wt%, or 25 wt% to 30 wt%.
[0213] In some embodiments, the encapsulated bead content in the sorbent polymer composite (SPC) includes a range of 10 wt% to 25 wt%, 10 wt% to 20 wt%, or 10 wt% to 15 wt%.
[0214] In some embodiments, the content of the encapsulated beads in the sorbent polymer composite (SPC) may be determined according to the total halogen source content desired in the sorbent polymer composite (SPC) and the total halogen source content in the encapsulated beads. In some embodiments, the encapsulated beads include a content of at least one halogen source of 1 wt% to 50 wt%.
[0215] In some embodiments, the encapsulated beads comprise a content of at least one halogen source of at least 1 wt%, at least 5 wt%, at least 10 wt%, at least 15 wt%, at least 20 wt%, at least 25 wt%, at least 30 wt%, at least 35 wt%, at least 40 wt%, or at least 45 wt%, or at least 50 wt%.
[0216] In some embodiments, the encapsulated beads comprise a content of at least one halogen source of 5 wt% to 50 wt%, 10 wt% to 50 wt%, 15 wt% to 50 wt%, 20 wt% to 50 wt%, 25 wt% to 50 wt%, 30 wt% to 50 wt%, 35 wt% to 50 wt%, 40 wt% to 50 wt%, or 45 wt% to 50 wt%.
[0217] In some embodiments, the encapsulated beads comprise a content of at least one halogen source of 1 wt% to 5 wt%, 1 wt% to 10 wt%, 1 wt% to 15 wt%, 1 wt% to 20 wt%, 1 wt% to 25 wt%, 1 wt% to 30 wt%, 1 wt% to 35 wt%, 1 wt% to 40 wt%, or 1 wt% to 45 wt%.
[0218] 5A illustrates a halogen reservoir in the form of an encapsulated bead 500 according to some non-limiting embodiments of the present disclosure. As shown, encapsulated bead 500 includes a core 501. In some embodiments, core 501 includes at least one particle, such as at least one carbon particle. In some embodiments, at least one halogen source (not shown) is present on at least a surface of core 501. In some embodiments, encapsulated bead 500 further includes at least one permeation control material 502. In some embodiments, permeation control material 502 encapsulates core 501.
[0219] FIG. 5B is an electronic image showing a collection of encapsulated beads 510 according to some non-limiting embodiments of the disclosure.
[0220] In some embodiments, the reservoir clusters are in the form of a plurality of discontinuous films embedded throughout the sorbent polymer composite (SPC).
[0221] Figures 6A and 6B are two sets of photographs illustrating various embodiments of halogen reservoirs incorporated into a sorbent polymer composite (SPC). Figure 6A is a surface photograph showing an article 600 including halogen reservoir clusters 620 comprised of halogen reservoir aggregates embedded within a sorbent polymer composite (SPC) 610 according to certain non-limiting embodiments of the disclosure. Figure 6B is a surface photograph showing an article 600 including halogen reservoirs 620 embedded within a sorbent polymer composite (SPC) 610 according to certain non-limiting embodiments of the disclosure. As shown, the halogen reservoir clusters 620 may be in the form of localized regions such as the streaks shown in Figure 6B. In some embodiments, the localized regions may be formed by creating an aggregate mixture of halogen reservoirs and embedding the aggregate mixture throughout the sorbent polymer composite (SPC) 610.
[0222] In some embodiments, the article comprises a quantity of the plurality of halogen reservoirs sufficient to result in a release rate of total halogens from the article that does not exceed 0.5% of the total halogens per day when a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days, the flue gas stream having a temperature of at least 20° C. and a relative humidity of at least 95%, and the flue gas stream having a concentration of at least one SO 2 species at least equal to 1 ppm. x compounds and at least 1 μg / m of the flue gas stream 3 and mercury vapor at a concentration of
[0223] In some embodiments, the article comprises a quantity of the plurality of halogen reservoirs sufficient to provide a release rate of total halogens from the article that does not exceed 2% of the total halogens per day when a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days, the flue gas stream having a temperature of at least 50° C. and a relative humidity of at least 95%, and the flue gas stream containing at least one SO 2 species at a concentration of at least 20 ppm. x compounds and at least 1 μg / m of the flue gas stream 3 and mercury vapor at a concentration of
[0224] In some embodiments, a sufficient amount of the halogen reservoirs in the article is between 5 wt% and 50 wt% of the halogen reservoirs based on the total weight of the article. In some embodiments, a sufficient amount of the halogen reservoirs in the article is at least 5 wt%, at least 10 wt%, at least 15 wt%, at least 20 wt%, at least 25 wt%, at least 30 wt%, at least 35 wt%, at least 40 wt%, at least 45 wt%, or at least 50 wt% of the halogen reservoirs based on the total weight of the article.
[0225] In some embodiments, a sufficient amount of the plurality of halogen reservoirs in the article is between 10 wt% and 50 wt% of the plurality of halogen reservoirs, based on the total weight of the article. In some embodiments, a sufficient amount of the plurality of halogen reservoirs in the article is between 15 wt% and 50 wt%, 20 wt% and 50 wt%, 25 wt% and 50 wt%, 30 wt% and 50 wt%, 35 wt% and 50 wt%, 40 wt% and 50 wt%, or 45 wt% and 50 wt% of the plurality of halogen reservoirs, based on the total weight of the article.
[0226] In some embodiments, a sufficient amount of the multiple halogen reservoirs in the article is between 5 wt% and 45 wt%, between 5 wt% and 40 wt%, between 5 wt% and 35 wt%, between 5 wt% and 30 wt%, between 5 wt% and 25 wt%, between 5 wt% and 20 wt%, between 5 wt% and 15 wt%, or between 5 wt% and 10 wt% of the multiple halogen reservoirs, based on the total weight of the article.
[0227] Some methods of the present disclosure relate to methods of obtaining an article comprising a sorbent polymer composite (SPC) and a plurality of halogen reservoirs.
[0228] In some embodiments, multiple halogen reservoirs are embedded within the SPC.
[0229] In some embodiments, each halogen reservoir of the plurality of halogen reservoirs comprises 5 wt% to 95 wt% of at least one permeation control material, based on the average weight of each halogen reservoir, and 5 wt% to 50 wt% of at least one halogen source, based on the average weight of each halogen reservoir.
[0230] Some such embodiments involve flowing a flue gas stream over at least one surface of the article for a period of at least 90 days, the gas stream having a temperature of at least 20° C. and a relative humidity of at least 95%, and the gas stream containing at least one SO 2 species at a concentration of at least 1 ppm. x Compounds and at least 1 μg / m based on the total volume of the flue gas stream 3 and mercury vapor at a concentration of
[0231] In some embodiments, the release rate of the total halogen in the article during the flow process does not exceed 0.5% of the total halogen in the article per day. In some embodiments, the release rate of the total halogen in the article during the flow process does not exceed 0.6% of the total halogen in the article per day, does not exceed 0.7% of the total halogen in the article per day, does not exceed 0.8% of the total halogen in the article per day, does not exceed 0.9% of the total halogen in the article per day, does not exceed 1% of the total halogen in the article per day, does not exceed 1.5% of the total halogen in the article per day, does not exceed 2% of the total halogen in the article per day.
[0232] In some embodiments, at least one of the plurality of halogen reservoirs is in the form of an encapsulated bead, as described above. In some such embodiments, the encapsulated bead is formed by obtaining at least one particle to form a core, depositing the at least one halogen source on at least a surface of the at least one particle, and encapsulating the core with the at least one permeation control material to form the encapsulated bead. In some embodiments, the at least one particle of the core comprises at least one carbon particle.
[0233] In some embodiments, the at least one halogen source is deposited as a solution onto at least the surface of the core. In some embodiments, the at least one halogen source is deposited as a solution onto at least the surface of the at least one carbon particle of the core.
[0234] In some embodiments, the at least one halogen source is deposited in a vapor phase onto at least a surface of the core. In some embodiments, the at least one halogen source is deposited in a vapor phase onto at least a surface of at least one carbon particle of the core.
[0235] In some embodiments, at least one of the plurality of halogen reservoirs is in the form of a reservoir particle, as described above. In some embodiments, the reservoir particle is formed by obtaining a permeation control material in the form of a permeation control particle and depositing at least one halogen source onto at least a surface of the permeation control particle.
[0236] In some embodiments, the method further comprises, after depositing the at least one halogen source on at least a surface of the permeation control particle, depositing a second permeation control material on at least a portion of the reservoir particle to form a second permeation control layer surrounding the at least one halogen source. In some embodiments, the first permeation control material and the second permeation control material comprise the same material. In some embodiments, the first permeation control material and the second permeation control material comprise different materials.
[0237] In some embodiments, the plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, each of the plurality of reservoir clusters being formed by mixing a plurality of carbon particles with at least one halogen source and at least one permeation control material to form a mixture, and embedding the mixture within the SPC.
[0238] In some embodiments, the method further comprises agglomerating the mixture to form an agglomerated mixture, and embedding the agglomerated mixture in SPC.
[0239] In some embodiments, the method further comprises forming the aggregate mixture into a plurality of discontinuous films and embedding the discontinuous films throughout the SPC.
[0240] Some embodiments of the present disclosure relate to a system including any of the exemplary articles and / or embodiments of the articles disclosed herein. In some embodiments, the system includes a passageway configured for the passage of a gas flow. In some embodiments, the article is housed within the passageway. In some embodiments, at least a portion of the article is disposed in contact with the flue gas.
[0241] FIG. 11 illustrates a non-limiting embodiment of a pollution control system 1100 having at least one of the articles described herein. Some non-limiting applications of the pollution control system 1100 may be for controlling air pollutant emissions to comply with various air pollutant emission standards. The pollution control system 1100 may be configured to capture elemental mercury and oxidized gas phase mercury from industrial flue gases. The pollution control system 1100 may include discrete stackable modules 1102. These modules may be provided downstream of a particle collection system. In some embodiments, the modules 1102 may be configured to include one or more embodiments of the articles 1104 (shown in an enlarged partial view in FIG. 11) described herein.
[0242] In some embodiments, the system can include several articles formed within a plurality of passages. In such embodiments, a gas stream can flow between the passages such that the gas stream directly contacts at least a portion of the SPC, but not directly contacts the reservoir. In some embodiments, the plurality of passages in the device can facilitate the flow of reactants, e.g., gaseous components, over one or more surfaces of the system and the discharge of at least one liquid product.
[0243] Non-limiting exemplary geometries of systems including the examples described herein can be found in U.S. Patent No. 9,381,459 to Stark et al., which is incorporated herein by reference in its entirety for all purposes.
[0244] 5 is a schematic diagram 1200 illustrating a flue gas stream flowing over a non-limiting embodiment of an article 1202 described herein. Article 1202 can capture both elemental and oxidized mercury from the flue gas stream as it flows past (e.g., over or through the material of article 1202). Mercury can be fixedly bound within the material of article 1202 via chemisorption. SO 2 Also adsorbs and / or absorbs (SO 2 The sulfuric acid can be catalyzed (via an oxidation catalyst) to liquid sulfuric acid. The liquid sulfuric acid can form droplets 1204 and be expelled from article 1202. The droplets 1204 can flow downward via gravity acting on the surface of article 1202.
[0245] Various examples and comparative examples of the article were tested to demonstrate the improved properties of the embodiments of the article incorporated within the embodied systems and processes also described herein, the results of which are detailed below.
[0246] Test Method
[0247] Simulated combustion exhaust gas flow durability test
[0248] The Simulated Flue Gas Stream Durability Test is a laboratory test. An exemplary test for simulated exposure to flue gas streams was conducted using an apparatus including: (1) an air supply regulated by a mass flow controller; (2) SO supplied by a gas cylinder containing a 1% sulfur dioxide / nitrogen mixture regulated through a mass flow controller 2 source, (3) A triangular sample cell with a side length of 12 mm and equipped with a bypass. This was placed in a furnace maintained at 65°C. (4) Maintain high relative humidity, >80%, using an MH-070 permeable tube humidifier (PermaPure, NJ, USA). 300 ppm / m 3 SO 2 The samples were exposed to a simulated flue gas stream containing 100% CO and 90% humidity at 1 standard liter / min in the above apparatus for a period of approximately 3 months. The total halogen (iodine) content of the samples was measured over time by X-ray fluorescence ("XRF") in wt %. The total halogen content of the samples was determined as the total iodine content. Thus, the discussion of halogen content and release rates is based on the iodine content of the samples and the release rate of total iodine (total halogens). The relative iodine content was tracked over time according to the formula C_iodine / C_iodine_0, where C_iodine / C_iodine_0 is the total iodine content in the item at a given time relative to the initial total iodine content in the item. The release rate of total halogens was analyzed by tracking the relative iodine content using an exponential release rate (decay) function according to the formula C_iodine / C_iodine_0 = exp(-k*time). where C_iodine is the total iodine content measured in each sample over time, C_iodine_0 is the initial total iodine content, and k is the iodine release rate (decay constant) constant with units of % / day. The total release rate is equal to k*C_iodine, and the relative release rate is equal to k*C_iodine / C_iodine_0.
[0249] The total release rate is equal to the release rate constant (e.g., 0.5% / day) multiplied by the total halogen in the article. In other words, the release rate of the total halogen from the article is, in this example, 0.5% of the total halogen in the article per day. The relative release rate and the release rate constant have the same units (% / day), but differ in value depending on the relative iodine content.
[0250] The iodine content was also tracked over time according to the formula C_iodine = C_iodine_0 * exp(-k*time), where C_iodine is the iodine content in the article, C_iodine_0 is the initial total iodine content, and k is the same iodine release rate (decay) constant as above with units of % / day. The exponential release rate (decay) model was used to estimate the depletion of the halogen source over time.
[0251] Combustion exhaust gas flow durability test
[0252] The flue gas stream durability test is a field test. An exemplary test was conducted in which an SPC sample (representing an article of the present disclosure) was exposed to a slipstream of a wet flue gas stream downstream from a desulfurization absorber at a coal-fired power plant, exposing the sample to the flue gas stream in two different configurations.
[0253] For the first configuration, six 3.5" x 12" (8.89 cm x 30.48 cm) SP laminate sheets were mounted into a 3.5" x 3.5" x 40" (8.89 cm x 8.89 cm x 101 cm) insulating sample fixture, supported on rods to allow unimpeded flow across the sheets. Approximately 80 ACFM (actual cubic feet per minute) (137 m 3 The samples were exposed to a flue gas flow of 1000 sq. m. / hr drawn by a fan through a series of tubes and into the sample fixture.
[0254] For the second configuration, 1.25" x 12" (3.175 cm x 30.48 cm) SPC laminate strips were installed onto frame fixtures 2' x 2' x 1' (61 cm x 61 cm x 30 cm) while the top and bottom of the strips were secured in place along rails of a frame capable of holding up to 100 strips. These rails were separated by 2 inches (50 mm) to provide unimpeded flow across the frame. The frame was inserted into a 2.1' x 2.1' x 8' (0.66m x 0.66m x 2.4m) insulated Pilot Tower Unit. Approximately 2880 ACFM (4860 m 3 The samples were exposed to a flue gas flow of 1000 sq. m / hr drawn in by a fan. Samples according to the present disclosure were tested in either the first or second configuration or both. In both configurations, the flow rate and pressure differential were monitored across the sample fixture. By nature, the composition of the slipstream flue gas stream was highly variable, but a typical composition of the flue gas stream was found to be between 2 μg / m mercury and 1000 sq. m. 3 , S.O. 2 Concentration is 20-40 ppm, O 2The concentration was 6%, NO concentration was 200 ppm, and relative humidity was >95%. The temperature of the slipstream flue gas stream was 50-55°C. Samples were taken approximately once a month (every 30 days) and the samples were analyzed for total halogen (iodine) content (wt%) by X-ray fluorescence ("XRF"). The total halogen content of the disclosed samples was determined as the total iodine content. Thus, the discussion of halogen content and release rate is based on the iodine content of the sample and the release rate of total iodine (total halogen). The total iodine content of each sample was converted to iodine content relative to the initial iodine content ("relative iodine content") and tracked over time as described in the table below. The release rate of total halogen corresponds to the release rate of iodine analyzed by the examples of the present invention. The release rate of total halogen was analyzed by tracking the relative iodine content using an exponential release rate (decay) function according to the following formula: The formula is C_iodine / C_iodine_0 = exp(-k*time), where C_iodine is the total iodine content in each sample, C_iodine_0 is the initial total iodine content, and k is the iodine release rate (content decay) constant. The total release rate is equal to k*C_iodine, and the relative release rate is equal to kC_iodine / C_iodine_0. An exponential release rate (decay) model was used to estimate the depletion of the halogen source over time.
[0255] Example 1
[0256] Iodine-filled carbon
[0257] Iodine-loaded carbon. Iodine on carbon was prepared by mixing 25% iodine (I) with 75% activated carbon (Norit PAC20BF, Cabot Inc., TX, USA). The mixture was heated to 60 °C in a sealed glass container for 4-6 h. The resulting iodine loading of the activated carbon was approximately 25 wt%.
[0258] Iodine loaded carbon 1B. Iodine loaded carbon was prepared by preparing a supersaturated solution of potassium iodide (KI) dissolved in water, adding activated carbon (NUCHAR SA-20, Ingevit, SC, USA) in a ratio of 75% KI solution:25% carbon, and stirring for approximately 10 minutes at 90° C. The carbon was then spread on a PTFE sheet and dried in an oven at 120° C. for 24 hours.
[0259] Halogen Reservoir Piece
[0260] Halogen reservoir strip 1A. A halogen reservoir slurry was prepared using 12% iodine loaded carbon 1A, 18% PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA), and 70% tetrahydrofuran (THF) solvent (I 2 -Carbon:PVDF=1:1.5). The slurry was then applied to a release liner by a slot die coating head to form a halogen reservoir film. The dried film thickness was 6 mils (0.1524 mm). The halogen reservoir film (e.g., a thin flat structure) was then cut into smaller, well-defined pieces using an office paper shredder, Fellowes Micro-Cut 16Ms Microshred Shredder (part number 4922002, Fellowes, Inc., Illinois, USA). The shreds had a square shape and an average size of approximately 4 mm x 13 mm (0.156 x 0.5 inches).
[0261] Halogen Reservoir Piece 1B. A 0.75 mm (30 mil) thick semi-continuous film or thin flat structure was produced by preparing a mixture of iodine loaded carbon 1A and PVDF powder (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in a ratio of 33% loaded carbon and 66% PVDF using the general dry blending method taught in U.S. Pat. No. 7,791,861 and a calendaring step at 110° C. The halogen reservoir film (e.g., thin flat structure) was then cut into smaller well-defined pieces using an office paper shredder, Fellowes Micro-Cut 16Ms Microshred Shredder (part number 4922002, Fellowes, Inc., IL, USA). The shreds had a rectangular shape and an average size of approximately 4 mm x 13 mm (0.156 x 0.5 inches).
[0262] Halogen Reservoir Piece 1C. A 0.75 mm (30 mil) thick semi-continuous film or thin flat structure was produced by preparing a mixture of iodine loaded carbon 1B and PVDF powder (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in a ratio of 40% loaded carbon and 60% PVDF using the general dry blending method taught in U.S. Pat. No. 7,791,861 and a calendaring step at 110° C. The halogen reservoir film (e.g., thin flat structure) was then cut into smaller, well-defined pieces using an office paper shredder, Fellowes Micro-Cut 16Ms Microshred Shredder (part number 4922002, Fellowes, Inc., IL, USA). The shreds had a rectangular shape and an average size of approximately 4 mm x 13 mm (0.156 x 0.5 inches).
[0263] Halogen reservoir piece 1D. A halogen reservoir material consisting of 40% KI (potassium iodide), 10% activated carbon (NUCHAR SA-20, Ingevit, South Carolina, USA), and 50% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) was made under laboratory conditions, and a 3 mm thick halogen reservoir part was manufactured by preparing the halogen reservoir material using the general dry blending method taught in U.S. Pat. No. 7,791,861, and using a calendaring process at 110° C., where the material melts. The halogen reservoir film (e.g., a thin flat structure) was then cut into smaller, well-defined pieces using an office paper shredder, Fellowes Micro-Cut 16Ms Microshred Shredder (part number 4922002, Fellowes, Inc., Illinois, USA). The shreds had a rectangular shape and an average size of approximately 4 mm x 13 mm (0.156 x 0.5 inches).
[0264] Halogen reservoir piece 1E. A halogen reservoir material consisting of 31% KI (potassium iodide), 6% activated carbon (NUCHAR SA-20, Ingevit, SC, USA), and 52% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., PA, USA) was made under laboratory conditions, and 2 mm thick halogen reservoir pieces were produced by preparing the halogen reservoir material using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring process at room temperature. These halogen reservoir pieces were then hand-shredded into various sizes ranging from approximately 2 cm x 2 cm to residual powder.
[0265] Halogen reservoir piece 1F. A halogen reservoir material consisting of 29% TBAI, 14% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 9% PTFE, and 48% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) was made under laboratory conditions, and 2 mm thick halogen reservoir pieces were manufactured by preparing the halogen reservoir material using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring process at room temperature. These halogen reservoir pieces were then cut into smaller, well-defined pieces using an office paper shredder, Fellowes 18-Sheet Cross-Cut 99Ci Powershred Commercial Shredder (part number 3229901, Fellowes, Inc., Illinois, USA). The shreds had a rectangular shape and an average size of approximately 4 mm x 38 mm (0.156 x 1.5 inches).
[0266] Halogen reservoir strip 1G. A halogen reservoir material consisting of 27% TBAI, 14% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 14% PTFE, and 45% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) was made under laboratory conditions, and 2 mm thick halogen reservoir pieces were manufactured by preparing the halogen reservoir material using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring process at room temperature. These halogen reservoir pieces were then cut into smaller pieces using an office paper shredder, Fellowes 18-Sheet Cross-Cut 99Ci Powershred Commercial Shredder (part number 3229901, Fellowes, Inc., Illinois, USA). The shreds had a rectangular shape and a nominal size of approximately 4 mm x 38 mm (0.156 x 1.5 inches).
[0267] Halogen reservoir piece 1H. A halogen reservoir material consisting of 20% TBAI, 20% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 20% PTFE, and 40% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) was made under laboratory conditions, and 2 mm thick halogen reservoir pieces were manufactured by preparing the halogen reservoir material using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring process at room temperature. These halogen reservoir pieces were then cut into smaller pieces using an office paper shredder, Fellowes 18-Sheet Cross-Cut 99Ci Powershred Commercial Shredder (part number 3229901, Fellowes, Inc., Illinois, USA). The shreds had a rectangular shape and a nominal size of approximately 4 mm x 38 mm (0.156 x 1.5 inches).
[0268] Halogen reservoir piece 1I. A halogen reservoir material consisting of 20% TBAI, 10% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 50% PTFE, and 20% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) was made under laboratory conditions, and 2 mm thick halogen reservoir pieces were manufactured by preparing the halogen reservoir material using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring process at room temperature. These halogen reservoir pieces were then cut into smaller pieces using an office paper shredder, Fellowes 18-Sheet Cross-Cut 99Ci Powershred Commercial Shredder (part number 3229901, Fellowes, Inc., Illinois, USA). The shreds had a rectangular shape and a nominal size of approximately 4 mm x 38 mm (0.156 x 1.5 inches).
[0269] Halogen reservoir piece 1J. A halogen reservoir material consisting of 10% TBAI, 5% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 5% PTFE, and 80% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) was made under laboratory conditions, and 2 mm thick halogen reservoir pieces were manufactured by preparing the halogen reservoir material using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring process at room temperature. These halogen reservoir pieces were then cut into smaller pieces using an office paper shredder, Fellowes 18-Sheet Cross-Cut 99Ci Powershred Commercial Shredder (part number 3229901, Fellowes, Inc., Illinois, USA). The shreds had a rectangular shape and a nominal size of approximately 4 mm x 38 mm (0.156 x 1.5 inches).
[0270] Halogen Reservoir Concentrate
[0271] Halogen Reservoir Agglomerate 1A. A halogen reservoir precursor agglomerate consisting of 8% TBAI, 5% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 23% PTFE, and 17% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) was made under laboratory conditions and a loose agglomerate was produced by preparing the halogen reservoir precursor using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0272] Halogen Reservoir Agglomerate 1B. A loose agglomerate was made by making a halogen reservoir precursor agglomerate consisting of 10% TBAI, 10% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 15% PTFE, and 65% permeation control material PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) under laboratory conditions and using the general dry blending method taught in U.S. Pat. No. 7,791,861 to prepare the halogen reservoir precursor agglomerate.
[0273] Sorbent Polymer Composite (SPC) Aggregates
[0274] SPC Agglomerate 1A. A loose agglomerate was produced by making a precursor agglomerate consisting of 67% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA) and 33% PTFE under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0275] SPC Agglomerate 1B. A loose agglomerate was produced by making a precursor agglomerate consisting of 64% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 31% PTFE, and 5% sulfur under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0276] SPC Agglomerate 1C. A loose agglomerate was produced by making a precursor agglomerate consisting of 70% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA) and 30% PTFE under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0277] SPC Agglomerate 1D. A loose agglomerate was produced by making a precursor agglomerate consisting of 76% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA) and 24% PTFE under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0278] SPC Agglomerate 1E. A loose agglomerate was produced by making a precursor agglomerate consisting of 63% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 27% PTFE, 4% TBAI, 4% sulfur, and 2% PVDF powder (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0279] SPC Agglomerate 1F. A loose agglomerate was produced by making a precursor agglomerate consisting of 68% activated carbon (Norit PAC20BF, Cabot Inc., TX, USA), 29% PTFE, and 3% PVDF (Kynar Flex 2751-00, Arkema Inc., PA, USA) under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0280] SPC Agglomerate 1G. A loose agglomerate was produced by making a precursor agglomerate consisting of 62% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 27% PTFE, 4% sulfur, 4% TBAI, and 3% PVDF (Kynar Flex 2751-00, Arkema Inc., Pennsylvania, USA) under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0281] SPC Agglomerate 1H. A loose agglomerate was produced by making a precursor agglomerate consisting of 64% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 27% PTFE, 4% sulfur (Sigma Aldrich), and 4% TBAI under laboratory conditions and preparing the precursor agglomerate using the general dry blending method taught in U.S. Pat. No. 7,791,861.
[0282] Sample 1A - Article containing SPC with halogen reservoir piece 1A. SPC agglomerate 1A was gently mixed by hand with halogen reservoir piece 1A in a ratio of 83% SPC agglomerate and 17% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 0.9 mm thick was produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 110° C.
[0283] Sample 1B - Article containing SPC with halogen reservoir piece 1B. SPC agglomerate 1B was gently inverted together with halogen reservoir piece 1B in a closed container in a ratio of 80% SPC agglomerate and 20% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 140°C.
[0284] Sample 1C - Article containing SPC with halogen reservoir piece 1B. SPC agglomerate 1B was gently inverted with halogen reservoir piece 1C in a closed container in a ratio of 80% SPC agglomerate and 20% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 140°C.
[0285] Sample 1D - Article containing SPC with halogen reservoir piece 1D. SPC aggregate 1C was gently inverted together with halogen reservoir piece 1D in a closed container to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 0.5 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0286] Sample 1E - Article containing SPC with halogen reservoir piece 1E. SPC agglomerate 1C was gently inverted with halogen reservoir piece 1E in a closed container in a ratio of 70% SPC agglomerate and 30% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1.2 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0287] Sample 1F - Article containing SPC with halogen reservoir piece 1F. SPC agglomerate 1D was gently inverted with halogen reservoir piece 1F in a closed container in a ratio of 67% SPC agglomerate and 33% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1.1 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0288] Sample 1G - Article containing SPC with Halogen Reservoir Agglomerate 1A. SPC Agglomerate 1E was gently inverted with Halogen Reservoir Agglomerate 1A in a closed container in a ratio of 50% SPC agglomerate and 50% Halogen Reservoir Agglomerate to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1.1 mm (44 mil) thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Patent No. 7,791,861 and a calendaring step at 145°C.
[0289] Sample 1H - Article containing SPC with halogen reservoir piece 1H. SPC agglomerate 1E was gently mixed by hand with halogen reservoir piece 1H in a ratio of 67% SPC agglomerate and 33% halogen reservoir piece to form a well-distributed mixture. Sorbent polymer composite (SPC) approximately 1 mm thick was produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0290] Sample 1I - Article containing SPC with halogen reservoir piece 1F. SPC agglomerate 1D was gently inverted with halogen reservoir piece 1F in a closed container in a ratio of 67% SPC agglomerate and 33% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1.1 mm (44 mil) thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0291] Sample 1J - Article containing SPC with halogen reservoir piece 1G. SPC agglomerate 1F was gently inverted with halogen reservoir piece 1G in a closed container in a ratio of 67% SPC agglomerate and 33% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1 mm (40 mil) thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0292] Sample 1K - Article containing SPC with halogen reservoir piece 1H. SPC agglomerate 1C was gently inverted with halogen reservoir piece 1H in a closed container in a ratio of 67% SPC agglomerate and 33% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 0.9 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0293] Sample 1L - Article containing SPC with halogen reservoir piece 1I. SPC agglomerate 1C was gently inverted with halogen reservoir piece 1I in a closed container in a ratio of 67% SPC agglomerate and 33% halogen reservoir piece to form a well-distributed mixture. A sorbent polymer composite (SPC) approximately 1 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0294] Sample 1M - Article containing SPC with Halogen Reservoir Agglomerate 1B. SPC Agglomerate 1G was gently inverted with Halogen Reservoir Agglomerate 1B in a closed container approximately 10 times to form a well-distributed mixture in a ratio of 33% SPC agglomerate and 67% Halogen Reservoir Agglomerate. A sorbent polymer composite (SPC) approximately 1 mm (40 mil) thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Patent No. 7,791,861 and a calendaring step at 145°C.
[0295] Sample 1N - Reservoir composite containing article consisting of halogen reservoir piece 1J. SPC aggregate 1H was gently inverted with halogen reservoir aggregate 1C in a closed container in a ratio of 67% SPC aggregate and 33% halogen reservoir aggregate to form a well-distributed mixture. Sorbent polymer composite (SPC) approximately 1 mm thick was then produced by preparing the mixture using the general dry blending method taught in U.S. Pat. No. 7,791,861 and using a calendaring step at 145°C.
[0296] Combustion exhaust gas flow durability test. Samples 1A, 1G, and 1I-1L were loaded into the above-mentioned combustion exhaust gas durability test, and the total iodine content was measured over time. The total iodine content was converted to the relative iodine content as described in Table 1 and FIG. 7. The release rate constant (iodine content decay constant k) was 0.17% / day for sample 1A, 0.17% / day for sample 1I, 0.34% / day for sample 1J, 0.38% / day for sample 1G, 0.23% / day for sample 1K, and 0.42% / day for sample 1L.
[0297] [Table 1]
[0298] Using an exponential release rate model (shown in FIG. 7 by the respective dashed lines), the flue gas stream durability data are extrapolated, with Samples 1J, 1G, and 1L exhibiting close to 2 years (approximately 550-700 days) of iodine release before approaching 90% depletion (shown by horizontal line L). The extrapolations for Samples 1A, 1I, and 1K show well over 3 years (1095 days) of iodine release before reaching 90% depletion.
[0299] Example 2
[0300] Encapsulated beads (Figure 5)
[0301] Iodine-PVDF-activated carbon (1:2:1) encapsulated bead 2A. The sample was prepared using a rotating disk atomization process. 40 grams (g) of PVDF (Kynar Flex 2751-00, Arkema Inc., PA, USA) were dissolved in 1695 grams of tetrahydrofuran (THF). A uniform suspension was formed by mixing 20 grams of activated carbon (Norit PAC20BF, Cabot Inc., TX, USA) with 20 grams of iodine (I). The suspension was then poured onto a 7.6 cm diameter disk at approximately 100-120 g / min. The disk was rotated at approximately 7000 rpm and atomized the slurry into a 0.1 cubic meter conical bottom tank heated to approximately 29°C. Air conveyed the dried powder through a cyclone for collection. 53.4 g of encapsulated beads were recovered. The resulting beads had a nominal particle size of 20-30 microns. A portion of the resulting beads were analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 20.7 wt% iodine. Such results indicated that the formulation of activated carbon with iodine retained the iodine within the finished encapsulated beads during the spray drying process.
[0302] Iodine-PVDF-activated carbon (1:1:2) encapsulated bead 2B. The sample was prepared using a rotating disk atomization process. 143 grams (g) of PVDF (Kynar Flex 2751-00, Arkema Inc., PA, USA) was dissolved in 2500 grams of tetrahydrofuran (THF). A uniform suspension was formed by dissolving 143 g of iodine (I) in the solution, followed by 286 grams of activated carbon (Norit PAC20BF, Cabot Inc., TX, USA). The suspension was then poured onto a 7.6 cm diameter disk at approximately 100-120 g / min. The disk was rotated at approximately 7000 rpm and atomized the slurry into a 0.1 cubic meter conical bottom tank heated to approximately 29°C. Air conveyed the dried powder through a cyclone for collection. After sieving through a 212 μm sieve, 544 g of microencapsulated beads were recovered. The resulting beads had a nominal particle size of 20-30 microns. A portion of the resulting beads was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 26.4 wt% iodine. According to the recipe above, the theoretical maximum iodine content in this mixture is 25 wt%. By increasing the carbon to polymer ratio to 2:1, virtually all of the iodine added to the formulation could be incorporated into the finished encapsulated beads.
[0303] Iodine-PVDF-activated carbon (1:2:1) encapsulated bead 2C. The sample was prepared using a rotating disk atomization process. 20 grams (g) of polycarbonate (catalog #954, MW 36,000, Scientific Polymer Products, Inc., NY, USA) were dissolved in 250 grams of methylene chloride (DCM). A uniform suspension was formed by dissolving 10 grams of iodine (I) in the solution, followed by 10 grams of activated carbon (Norit PAC20BF, Cabot Inc., TX, USA). The suspension was then poured onto a 7.6 cm diameter disk at approximately 100-120 g / min. The disk was rotated at approximately 7000 rpm and the slurry was atomized into a 0.1 cubic meter conical bottom tank heated to approximately 40°C. Air conveyed the dried powder through a cyclone for collection. After sieving through a 212 μm sieve, 33.2 g of encapsulated beads were recovered. The nominal particle size of the resulting beads was 20-30 microns. A portion of the resulting beads was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 21.3 wt% iodine. According to the recipe above, the maximum iodine content in this mixture is theoretically 25 wt%.
[0304] Iodine-Ethylcellulose-Activated Carbon (1:2:1) Encapsulated Beads 2D. The sample was prepared using a rotating disk atomization process. 20 grams (g) of ethylcellulose (Ethocel Standard 4, DuPont de Nemours, Delaware, USA) were dissolved in 330 g of methanol (MeOH). A uniform suspension was formed by dissolving 10 g of iodine (I) in the solution, followed by 10 g of activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA). The suspension was then poured onto a 7.6 inch diameter disk at approximately 100-120 g / min. The disk was rotated at approximately 7000 rpm and atomized the slurry into a 0.1 cubic meter conical bottom tank heated to approximately 29°C. Air conveyed the dried powder through a cyclone for collection. After sieving through a 212 μm sieve, 36 grams of encapsulated beads were recovered. The nominal particle size of the resulting beads was 20-30 microns. A portion of the resulting beads was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 23.3 wt% iodine. According to the recipe above, the maximum theoretical iodine content in this mixture is 25 wt%.
[0305] Sorbent Polymer Composites of Encapsulated Beads Samples 2A-2C. A sorbent polymer composite consisting of 67% activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 22% PTFE, and 11% encapsulated beads was made under laboratory conditions, and the composite samples were formed by preparing the sorbent polymer composite using the general dry blending method taught in U.S. Pat. No. 7,791,861. As summarized in Table 2, sorbent polymer composite (SPC) Samples 2A-2C were formulated using the encapsulated beads described in Examples 2B-2D, respectively. Portions of the SPC samples were analyzed by X-ray fluorescence ("XRF") analysis to ensure that iodine was retained during processing. The results are shown in Table 2.
[0306] [Table 2]
[0307] To provide sufficient stiffness for field testing, two 3.5" x 12" strips of each material were laminated using 2 mil PVDF film (SOLEF PVDF 9009, Solvay Specialty Polymers, LLC, Delaware, USA) in a belt laminator at approximately 170°C and roller pressures of approximately 60-80 psig.
[0308] Flue Gas Stream Durability Test. Samples 2A-I, 2A-II, 2B, and 2C were loaded into the flue gas stream durability test described above, and the total iodine content was measured over time. The total iodine content was converted to the iodine content relative to the initial iodine content, as listed in Table 3.
[0309] The halogen release rate constant k (iodine decay rate) was determined to be 0.58% / day for Sample 2A-I, 0.49% / day for Sample 2A-II, 0.75% / day for Sample 2B, and 0.76% / day for Sample 2C, as shown in Table 3 and Figure 8. Using an exponential release rate model (shown in Figure 8 by the respective dashed lines), extrapolation of the flue gas stream durability data indicates that Sample 2A-I reached 90% iodine depletion in about 450 days and Sample 2A-II reached 90% iodine depletion in about 400 days, while Samples 2B and 2C reached 90% iodine depletion after about 300 days. [Table 3]
[0310] Example 3
[0311] Iodine-loaded reservoir particles
[0312] Iodine-loaded reservoir particles 3A. Iodine-loaded polystyrene particles were prepared by mixing 20% iodine with 80% polystyrene (PS) beads (Poly-Fil Micro Beads, part number PFMB, Fairfield Processing Corp., Connecticut, USA) by shaking the mixing container several times for 1 hour to mix the iodine and beads. The mixture was then heated to 80° C. in a closed container for 20 hours. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 20.2 wt% iodine.
[0313] Iodine-loaded reservoir particle 3B. Cross-linked polystyrene-divinylbenzene (PS-DVB) beads (Amberlite XAD4, Sigma-Aldrich, MO, USA) were dispersed in a glass baking dish and placed in a 120° C. oven until completely dry. The dried beads were then mixed with iodine in a ratio of 75% and 25% by shaking the mixing vessel several times for 1 hour. The mixture was then heated to 80° C. in a closed vessel for 16 hours. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 24.3 wt. % iodine.
[0314] Iodine loaded reservoir particle 3B. Cross-linked polystyrene-divinylbenzene (PS-DVB) beads (Amberlite XAD4, Sigma-Aldrich, MO, USA) were washed multiple times to remove impurities that may affect mercury removal performance. 500 mL of deionized water and 200 grams of PS-DVB beads were added to a 1000 mL beaker and then vacuum filtered. This washing procedure was repeated three times. The washed beads were then dispersed in a glass baking dish and placed in a 120° C. oven until completely dry. The dried beads were then mixed with iodine in a ratio of 75% and 25% by shaking the mixing vessel several times for one hour. The mixture was then heated to 80° C. in a closed vessel for 16 hours. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 24.5 wt. % iodine.
[0315] Permeation Control Material
[0316] Solution 3A. A solution consisting of 1.5 wt % PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in tetrahydrofuran (THF) solvent was prepared.
[0317] Solution 3B. A solution consisting of 4.0 wt % PVDF (Kynar Superflex 2501-20, Arkema Inc., PA, USA) in acetone (ACE) solvent was prepared.
[0318] Iodine loaded particles with permeation control material
[0319] Coated reservoir particles 3A. The polymer layer can be added to the particles by any method known to one skilled in the art. One such process is fluidized bed coating. Solution 3A was applied to iodine-loaded reservoir particles 3B using a Fluid Air Feasibility Processor, a laboratory-scale fluidized bed coater using a 1 L chamber with a bottom spray. The unit was initially charged with 100 g of iodine-loaded beads 3B. The inlet temperature of the fluidized bed coater was set at 35°C. This resulted in an outlet temperature of 25.3-29.1°C and a product temperature of 24.8-28.1°C. The inlet air flow rate was set at 25-30 standard cubic feet per hour (SCFH), the atomizing air at 12 psig, and the filter pressure at 98 psig. Permeation control material solution 3A was pumped into the atomizing nozzle at 2.5 g / min in a continuous coating run until approximately 20% PVDF was loaded.
[0320] Coated Reservoir Particles 3B. Solution 3B was applied to iodine-loaded reservoir particles 3C using a Fluid Air Feasibility Processor, a laboratory-scale fluidized bed coater using a 1 L chamber with a bottom spray. The unit was initially charged with 75 g of iodine-loaded beads 3B. The inlet temperature of the fluidized bed coater was set at 45°C. This resulted in an outlet temperature of 36.6-38.3°C and a product temperature of 39.1-40.2°C. The inlet air flow rate was set at 26-28 SCFH, atomizing air at 12 psig, and filter pressure at 95 psig. Permeation control material solution 3A was pumped into the atomizing nozzle at 2.1 g / min in a continuous coating run until approximately 50% PVDF was filled.
[0321] Brunauer-Emmett-Teller (BET) surface area Brunauer-Emmett-Teller (BET) surface area
[0322] To verify the coverage of the permeation control material coating, the specific surface area of the particles was measured by nitrogen adsorption (BET). The BET surface area of the iodized PS-DVB particles decreases with increasing coverage of the permeation control material coating. The uncoated particles have a BET surface area of 631.4 m. 2 / g, whereas the coated reservoir particle 3B had a BET surface area of 8.8 m 2 / g. The reduction in surface area demonstrated that the coated reservoir particles 3B were fully covered with the permeation control material.
[0323] Iodine Stability Test
[0324] The stability of the iodine-loaded and coated particles was tested by exposing the samples to heat inside a 60°C oven for three months. The iodine-loaded and coated particle samples were placed in vials and then closed with a cap. The vials also contained activated charcoal to capture lost iodine. The iodine content of the iodine-loaded and coated particles before and after testing was determined by XRF. After three months (94-97 days), the percent iodine loss was 13.9% for iodine-loaded reservoir particles 3B, 6.9% for coated reservoir particles 3A, and 2.1% for coated reservoir particles 3B.
[0325] Sample with reservoir particles
[0326] Sample 3A - Article containing SPC with iodine loaded reservoir particles 3A. A composite sample was formed by making a sorbent polymer composite (SPC) consisting of 65 parts activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 20 parts PTFE, and 5 parts iodine loaded reservoir particles 3A under laboratory conditions and preparing the sorbent polymer composite (SPC) using the general dry blending method taught in U.S. Patent No. 7,791,861. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 1.11 wt% iodine.
[0327] Sample 3B - Article containing SPC with iodine loaded reservoir particles 3B. A composite sample was formed by making a sorbent polymer composite (SPC) consisting of 65 parts activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 20 parts PTFE, and 15 parts iodine loaded reservoir particles 3B under laboratory conditions and preparing the sorbent polymer composite (SPC) using the general dry blending method taught in U.S. Patent No. 7,791,861. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 3.75 wt% iodine.
[0328] Sample 3C - Article containing SPC with Coated Reservoir Particles 3A. A composite sample was formed by making a sorbent polymer composite (SPC) consisting of 65 parts activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 20 parts PTFE, and 15 parts coated reservoir particles 3A under laboratory conditions and preparing the sorbent polymer composite (SPC) using the general dry blending method taught in U.S. Patent No. 7,791,861. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 2.429 wt% iodine.
[0329] Sample 3D - Article containing SPC with Coated Reservoir Particles 3B. A composite sample was formed by making a sorbent polymer composite (SPC) consisting of 65 parts activated carbon (Norit PAC20BF, Cabot Inc., Texas, USA), 20 parts PTFE, and 15 parts coated reservoir particles 3B under laboratory conditions and preparing the sorbent polymer composite (SPC) using the general dry blending method taught in U.S. Patent No. 7,791,861. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 1.18% iodine.
[0330] Scanning Electron Micrograph. A scanning electron micrograph (SEM) image of sample 3C is shown in Figure 3B. Figure 3B shows in cross section two coated reservoir particles 305 embedded within SPC material 303. It can be observed that the particles 305 are intact and the PVDF permeation control material coating is visible after formation within the SPC.
[0331] Sample 3E - An article comprising laminated SPC with iodine-loaded reservoir particles 3B. Two SPC layers of Sample 3B were laid down and laminated on a belt laminator using 36-40 psig pressure and 185° C. A portion of the sample was analyzed by X-ray fluorescence ("XRF") analysis and shown to contain approximately 3.74 wt % iodine.
[0332] Simulated flue gas stream durability test. Three samples of Sample 3E were exposed to the simulated flue gas stream for a period of one month. The iodine content before and after the test is measured by X-ray fluorescence ("XRF") analysis. The three samples exhibited relative iodine contents of 0.24, 0.47, and 0.64, respectively, over the course of the test.
[0333] Flue Gas Stream Durability Testing. Data for Sample 3E is summarized in Table 5, which shows the relative iodine content of the SPC with iodized beads after being tested for flue gas durability under flue gas stream conditions.
[0334] [Table 4]
[0335] Comparative Example 1
[0336] SPC Comparative Sample 4A. A sorbent polymer composite (SPC) consisting of 40% activated carbon (NUCHAR SA-20, Ingevit, South Carolina, USA), 50% PTFE, 3% potassium iodide (KI) as a halogen source, and 7% sulfur was prepared under laboratory conditions and the composite sample was formed by preparing the sorbent polymer composite (SPC) using the general dry blending method taught in U.S. Patent No. 7,791,861. The composite sample was then uniaxially stretched according to the teachings of U.S. Patent No. 3,953,566.
[0337] SPC Comparative Sample 4B. A composite sample was formed by making a Sorbent Polymer Composite (SPC) consisting of 50% activated carbon (NUCHAR SA-20, Ingevit, South Carolina, USA), 39% PTFE, 6% tetrabutylammonium iodide (TBAI) as the halogen source, and 5% sulfur under laboratory conditions and using the general dry blending method taught in U.S. Pat. No. 7,791,861 to prepare the Sorbent Polymer Composite (SPC).
[0338] Simulated Flue Gas Stream Durability Testing. SPC Comparative Samples 4A and 4B were loaded into the flue gas stream durability testing and the relative iodine content was tracked over time as described in Table 6. The halogen release rate constant (iodine content decay constant k) was determined to be 17.7% / day for SPC Comparative Sample 4A and 16.3% / day for SPC Comparative Sample 4B as shown in FIG. 9. FIG. 9 shows the relative iodine content measured over a 14 day period. Using an exponential release rate (decay) model also shown in FIG. 9 by the respective dashed lines, extrapolation of the flue gas stream durability data indicates that SPC Comparative Samples 4A and 4B only exhibited about 15 days of iodine release before approaching 90% depletion (shown by horizontal line L).
[0339] [Table 5]
[0340] Flue Gas Stream Durability Testing. SPC Comparative Samples 4A and 4B were loaded during the flue gas stream durability test. The relative iodine content was tracked over time as described in Table 7. The halogen release rate constant (iodine content decay constant k) was determined to be 15% / day for SPC Comparative Sample 4A and 9.0% / day for SPC Comparative Sample 4B. As shown in Table 7 and Figure 10, Comparative Samples 4A and 4B reach 90% iodine depletion (indicated by horizontal line L) in less than 10 days. The relative iodine content in Figure 10 was measured over 24 and 51 days, respectively.
[0341] [Table 6]
[0342] Aspects
[0343] Various embodiments are described below. It should be understood that any one or more of the features listed in the embodiments below may be combined with any one or more of the other embodiments. Aspect 1 Sorbent Polymer Composites (SPC), and Multiple Halogen Reservoirs An article comprising: the plurality of halogen reservoirs are embedded within the SPC; and Each halogen reservoir of the plurality of halogen reservoirs comprises: 5 wt% to 95 wt% of at least one permeation control material, based on the average weight of each halogen reservoir; 5 wt% to 50 wt% of at least one halogen source based on the average weight of each halogen reservoir; An article comprising: Aspect 2 The article of embodiment 1, wherein the SPC comprises a polymeric material. Aspect 3 3. The article of embodiment 2, wherein the polymeric material comprises at least one of polyfluoroethylene propylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), a terpolymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride (THV), polychlorofluoroethylene (PCFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyethylene, polyparaxylylene (PPX), polylactic acid (PLLA), polyethylene (PE), expanded polyethylene (ePE), polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), or any combination thereof. Aspect 4 The article of embodiment 2, wherein the polymeric material comprises PVDF. Aspect 5 The article of embodiment 4, wherein the PVDF is a PVDF homopolymer. Aspect 6 The article of embodiment 4, wherein the PVDF is a PVDF copolymer. Aspect 7 The article of embodiment 6, wherein the PVDF copolymer is a copolymer of PVDF and hexafluoropropylene (HFP). Aspect 8 The article of embodiment 3, wherein the polymeric material comprises PTFE. Aspect 9 The article of embodiment 3, wherein the polymeric material comprises ePTFE. Aspect 10 The article of any of embodiments 2-9, wherein the polymeric material comprises fibrils and nodes, and wherein the polymeric material becomes porous upon stretching such that voids form between the fibrils and nodes. Aspect 11 11. The article of any of the preceding embodiments, wherein the at least one halogen source comprises at least a metal halide, an ammonium halide, an elemental halogen, or any combination thereof. Aspect 12 11. The article of any of the preceding embodiments, wherein the at least one halogen source comprises at least sodium chloride, potassium chloride, sodium bromide, potassium bromide, sodium iodide, potassium iodide, or any combination thereof. Aspect 13 The article of any of the preceding embodiments, wherein the at least one halogen source comprises at least an ammonium halide. Aspect 14 11. The article of any of the preceding embodiments, wherein the at least one halogen source comprises at least tetramethylammonium iodide, tetrabutylammonium iodide, tetraethylammonium iodide, tetrapropylammonium iodide, tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium triiodide, tetrabutylammonium tribromide, tetrabutylammonium trichloride, tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, or any combination thereof. Aspect 15 11. The article of any of the preceding embodiments, wherein the at least one halogen source comprises at least an elemental halogen. Aspect 16 The elemental halogen is elemental iodine (I2 ), elemental chlorine (Cl 2 ), elemental bromine (Br 2 16. The article of embodiment 15, wherein the at least one of Aspect 17 11. The article of any of the preceding embodiments, wherein the at least one halogen source comprises tetrabutylammonium iodide (TBAI). Aspect 18 The article of any of the preceding embodiments, wherein the at least one halogen source comprises potassium iodide (KI). Aspect 19 11. The article of any of the preceding embodiments, wherein the at least one halogen source comprises at least one phosphonium halide. Aspect 20 The at least one phosphonium halide may be tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI), 3 20. The article of embodiment 19, wherein the at least one phosphonium halide comprises tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPBr), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof. In some embodiments, the at least one phosphonium halide comprises tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI), or any combination thereof. 3 ), tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof. Aspect 21 The article of embodiment 20, wherein the at least one phosphonium halide is ETPPI. Aspect 22 wherein the article comprises a plurality of halogen reservoirs in an amount sufficient to provide a release rate of total halogen from the article of not more than 2% per day relative to the total halogen in the article under conditions in which a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days; the flue gas stream has a temperature of at least 20° C. and a relative humidity of at least 95%; and The gas stream contains at least one SO 2 species at a concentration of at least 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of 22. The article of any one of claims 1 to 21. Aspect 23 at least one of the plurality of halogen reservoirs is in the form of an encapsulated bead; The encapsulated beads are A core, the at least one halogen source, the at least one halogen source being present on at least a surface of the core; the permeation control material, the permeation control material encapsulating the core; 23. The article of any one of claims 1 to 22, comprising: Aspect 24 24. The article of embodiment 23, wherein the core comprises activated carbon. Aspect 25 at least one of the plurality of halogen reservoirs is in the form of a reservoir particle; The reservoir particles are the permeation control material, wherein the permeation control material is in the form of permeation control particles; the at least one halogen source, wherein the at least one halogen source is present at least on a surface of the permeation control particle; 25. The article of any of the preceding claims, comprising: Aspect 26 26. The article of embodiment 25, wherein the permeation control material comprises polystyrene, cross-linked polystyrene-divinylbenzene (PS-DVB), or a combination thereof. Aspect 27 27. The article of embodiment 25 or 26, wherein the reservoir particle further comprises a second permeation control material, the second permeation control material surrounding the at least one halogen source on a surface of the permeation control particle. Aspect 28 the plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, each of the reservoir clusters comprising: said at least one halogen source; The permeation control material; 23. The article of any of the preceding claims, comprising: Aspect 29 30. The article of embodiment 28, wherein the plurality of reservoir clusters are in the form of a plurality of halogen reservoir pieces embedded throughout the SPC. Aspect 30 29. The article of embodiment 28, wherein the plurality of reservoir clusters are in the form of a plurality of halogen reservoir agglomerates mixed with SPC. Aspect 31 23. The article of embodiment 22, wherein the sufficient amount of the plurality of halogen reservoirs is between 5% and 75% by weight of the plurality of halogen reservoirs based on a total weight of the article. Aspect 32 23. The article of embodiment 22, wherein the sufficient amount of the plurality of halogen reservoirs is between 5% and 50% by weight of the plurality of halogen reservoirs based on a total weight of the article. Aspect 33 wherein the article comprises a plurality of halogen reservoirs in an amount sufficient to provide a release rate of total halogen from the article that does not exceed 0.5% of the total halogen in the article per day under conditions in which a flue gas stream is flowed over at least one surface of the article for a period of at least 90 days; the flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%; and The gas stream contains at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of. Aspect 34 Obtaining a sorbent polymer composite (SPC), and Obtaining a plurality of halogen reservoirs; wherein each reservoir of the plurality of halogen reservoirs comprises: 5 wt% to 95 wt% of at least one permeation control material, based on the average weight of each halogen reservoir; 5 wt% to 50% of at least one halogen source based on the average weight of each halogen reservoir; and forming an article having said plurality of halogen reservoirs embedded within said SPC The method includes: Aspect 35 At least one of the plurality of halogen reservoirs is in the form of an encapsulated bead, and the method further comprises: Obtaining at least one particle forming a core, depositing the at least one halogen source onto a surface of the at least one particle; and Encapsulating the core with the at least one permeation control material to form the encapsulated bead. to form the encapsulated bead. The method of embodiment 34, further comprising: Aspect 36 The method of embodiment 35, wherein the at least one halogen source is deposited onto the surface of the at least one particle as a solution. Aspect 37 The method of embodiment 35, wherein the at least one halogen source is deposited onto the surface of the at least one particle in a gas phase. Aspect 38 The article of any one of embodiments 35 to 37, wherein the at least one particle is a carbon particle. Aspect 39 at least one of the plurality of halogen reservoirs is in the form of a reservoir particle; The reservoir particles are obtaining said at least one permeation control material in the form of permeation control particles; and depositing at least one halogen source on the surface of said permeation control particles; It is formed by The method of embodiment 35. Aspect 40 The method further comprising: After depositing the at least one halogen source on the surface of the permeation control particle, a second permeation control material is deposited on at least a portion of the reservoir particle to form a second permeation control layer surrounding the at least one halogen source. The method of embodiment 39, further comprising: Aspect 41 The plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, and the method comprises: combining a plurality of particles with at least one halogen source and at least one permeation control material to form a mixture; forming the mixture into a film or part; forming the film or part into a halogen reservoir piece; and Embedding the halogen reservoir piece into the SPC forming each of the plurality of reservoir clusters by The method of embodiment 34, further comprising: Aspect 42 The plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, and the method comprises: Obtaining SPC aggregates, forming a reservoir aggregate by combining a plurality of particles with at least one halogen source and at least one permeation control material; and The SPC aggregate is mixed with the reservoir aggregate to form the article. forming each of the plurality of reservoir clusters by The method of embodiment 34, further comprising: Aspect 43 The method further comprises flowing a flue gas stream through the article, wherein the flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%, and wherein the flue gas stream contains at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m based on the total volume of said flue gas stream. 3and mercury vapor at a concentration of from about 0.5% to about 1.0%, wherein the release rate of the total halogens in the article does not exceed 0.5% of the total halogens in the article per day.
[0344] It should be understood that changes may be made in details, particularly in materials of construction employed, and in the shape, size and arrangement of parts without departing from the scope of the present disclosure. The specification and described embodiments are by way of example only, with the true scope and spirit of the disclosure being indicated by the following claims.
Claims
1. Sorbent Polymer Composites (SPC), and Multiple Halogen Reservoirs An apparatus for treating a combustion exhaust gas, comprising: the plurality of halogen reservoirs are embedded within the SPC; and Each halogen reservoir of the plurality of halogen reservoirs comprises: 5 wt % to 95 wt % of at least one permeation control material, based on the average weight of each halogen reservoir; 5 wt % to 50 wt % of at least one halogen source, based on the average weight of each halogen reservoir; An apparatus comprising:
2. The device of claim 1 , wherein the SPC comprises a polymeric material.
3. 3. The device of claim 2, wherein the polymeric material comprises at least one of polyfluoroethylene propylene (PFEP), polyperfluoroacrylate (PPFA), polyvinylidene fluoride (PVDF), a terpolymer of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride (THV), polychlorotrifluoroethylene (PCTFE), poly(ethylene-co-tetrafluoroethylene) (ETFE), ultra-high molecular weight polyethylene (UHMWPE), polyethylene, polyparaxylylene (PPX), polylactic acid (PLA), polyethylene (PE), expanded polyethylene (ePE), polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), or any combination thereof.
4. The device of claim 2 , wherein the polymeric material comprises PVDF.
5. The device of claim 4 , wherein the PVDF is a PVDF homopolymer.
6. The device of claim 4 , wherein the PVDF is a PVDF copolymer.
7. The device of claim 6 , wherein the PVDF copolymer is a copolymer of PVDF and hexafluoropropylene (HFP).
8. The device of claim 3 , wherein the polymeric material comprises PTFE.
9. The device of claim 3 , wherein the polymeric material comprises ePTFE.
10. 10. The device of claim 2, wherein the polymeric material comprises fibrils and nodes, and the polymeric material becomes porous upon stretching such that voids are formed between the fibrils and nodes.
11. 11. The apparatus of claim 1, wherein the at least one halogen source comprises at least a metal halide, an ammonium halide, an elemental halogen, or any combination thereof.
12. 11. The apparatus of any one of claims 1 to 10, wherein the at least one halogen source comprises at least sodium chloride, potassium chloride, sodium bromide, potassium bromide, sodium iodide, potassium iodide, or any combination thereof.
13. 11. The apparatus of claim 1, wherein the at least one halogen source comprises at least an ammonium halide.
14. 11. The device of any one of claims 1 to 10, wherein the at least one halogen source comprises at least tetramethylammonium iodide, tetrabutylammonium iodide, tetraethylammonium iodide, tetrapropylammonium iodide, tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium triiodide, tetrabutylammonium tribromide, tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, or any combination thereof.
15. 11. The apparatus of claim 1, wherein the at least one halogen source comprises at least an elemental halogen.
16. The elemental halogen is elemental iodine (I 2 ), elemental chlorine (Cl 2 ), elemental bromine (Br 2 16. The device of claim 15, wherein the at least one of
17. 11. The apparatus of any one of claims 1 to 10, wherein the at least one halogen source comprises tetrabutylammonium iodide (TBAI).
18. 11. The apparatus of claim 1, wherein the at least one halogen source comprises potassium iodide (KI).
19. 11. The apparatus of claim 1, wherein the at least one halogen source comprises at least one phosphonium halide.
20. The at least one phosphonium halide may be tetrabutylphosphonium iodide (TBPI), ethyltriphenylphosphonium triiodide (ETPPI), 3 20. The device of claim 19, comprising: tetrabutylphosphonium bromide (TBPBr), ethyltriphenylphosphonium bromide (ETPPBr), ethyltriphenylphosphonium iodide (ETPPI), or any combination thereof.
21. 21. The apparatus of claim 20, wherein the at least one phosphonium halide is ETPPI.
22. said apparatus comprising a plurality of halogen reservoirs in an amount sufficient to provide a release rate of total halogen from the apparatus that does not exceed 2% of the total halogen in the apparatus per day under conditions in which a flue gas stream is flowed over at least one surface of the apparatus for a period of at least 90 days; the flue gas stream has a temperature of at least 20° C. and a relative humidity of at least 95%; and The flue gas stream is at least one SO having a concentration of at least 1 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of
23. at least one of the plurality of halogen reservoirs is in the form of an encapsulated bead; The encapsulated beads are A core, the at least one halogen source, the at least one halogen source being present on at least a surface of the core; the permeation control material, the permeation control material encapsulating the core; 23. The apparatus of any one of claims 1 to 22, comprising:
24. 24. The device of claim 23, wherein the core comprises activated carbon.
25. at least one of the plurality of halogen reservoirs is in the form of a reservoir particle; The reservoir particles are the permeation control material, wherein the permeation control material is in the form of permeation control particles; the at least one halogen source, the at least one halogen source being present at least on a surface of the permeation control particle; 25. The apparatus of claim 1 , comprising:
26. 26. The device of claim 25, wherein the permeation control material comprises polystyrene, cross-linked polystyrene-divinylbenzene (PS-DVB), or a combination thereof.
27. 27. The device of claim 25 or 26, wherein the reservoir particle further comprises a second permeation control material, the second permeation control material surrounding the at least one halogen source on a surface of the permeation control particle.
28. the plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, each of the reservoir clusters comprising: said at least one halogen source; The permeation control material; 23. The apparatus of any one of claims 1 to 22, comprising:
29. 30. The device of claim 28, wherein the plurality of reservoir clusters are in the form of a plurality of halogen reservoir pieces embedded throughout the SPC.
30. 30. The apparatus of claim 28, wherein the plurality of reservoir clusters are in the form of a plurality of halogen reservoir aggregates mixed with SPC.
31. 23. The device of claim 22, wherein the sufficient amount of the plurality of halogen reservoirs is between 5% and 75% by weight of the plurality of halogen reservoirs based on the total weight of the device.
32. 23. The device of claim 22, wherein the sufficient amount of the plurality of halogen reservoirs is between 5% and 50% by weight of the plurality of halogen reservoirs based on the total weight of the device.
33. said apparatus comprising a plurality of halogen reservoirs in an amount sufficient to provide a release rate of total halogen from said apparatus that does not exceed 0.5% of the total halogen in said apparatus per day under conditions in which a flue gas stream is flowed over at least one surface of said apparatus for a period of at least 90 days; the flue gas stream has a temperature of at least 50° C. and a relative humidity of at least 95%; and The flue gas stream is at least one SO 2 species having a concentration of at least 20 ppm. x and at least 1 μg / m of said flue gas stream. 3 and mercury vapor at a concentration of 33. Apparatus according to any one of claims 1 to 32.
34. Obtaining a sorbent polymer composite (SPC), and Obtaining a plurality of halogen reservoirs; wherein each reservoir of the plurality of halogen reservoirs comprises: 5 wt % to 95 wt % of at least one permeation control material, based on the average weight of each halogen reservoir; 5 wt % to 50 wt % of at least one halogen source, based on the average weight of each halogen reservoir; and forming an apparatus for treating a combustion exhaust gas having the plurality of halogen reservoirs embedded within the SPC; The method includes:
35. At least one of the plurality of halogen reservoirs is in the form of an encapsulated bead, and the method further comprises: Obtaining at least one particle forming a core; depositing said at least one halogen source onto a surface of said at least one particle; and encapsulating the core with the at least one permeation control material to form the encapsulated bead; 35. The method of claim 34, further comprising:
36. 36. The method of claim 35, wherein the at least one halogen source is deposited onto the surface of the at least one particle as a solution.
37. 36. The method of claim 35, wherein the at least one halogen source is deposited onto the surface of the at least one particle in a vapor phase.
38. 38. The method of any one of claims 35 to 37, wherein the at least one particle is a carbon particle.
39. at least one of the plurality of halogen reservoirs is in the form of a reservoir particle; The reservoir particles are obtaining said at least one permeation control material in the form of permeation control particles; and depositing at least one halogen source on the surface of said permeation control particles; 36. The method of claim 35, wherein the compound is formed by:
40. The method further comprising: After depositing the at least one halogen source on the surface of the permeation control particle, a second permeation control material is deposited on at least a portion of the reservoir particle to form a second permeation control layer surrounding the at least one halogen source.
40. The method of claim 39, further comprising:
41. The plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, and the method comprises: combining a plurality of particles with at least one halogen source and at least one permeation control material to form a mixture; forming the mixture into a film or part; forming the film or part into a halogen reservoir piece; and Embedding the halogen reservoir piece into the SPC forming each of the plurality of reservoir clusters by 35. The method of claim 34, further comprising:
42. The plurality of halogen reservoirs are in the form of a plurality of reservoir clusters, and the method comprises: Obtaining SPC aggregates, forming a reservoir aggregate by combining a plurality of particles with at least one halogen source and at least one permeation control material; and Mixing the SPC aggregate with the reservoir aggregate to form the device. forming each of the plurality of reservoir clusters by 35. The method of claim 34, further comprising:
43. The method further comprises flowing a flue gas stream through the device, the flue gas stream having a temperature of at least 50° C. and a relative humidity of at least 95%, the flue gas stream comprising at least one SO 2 species at a concentration of at least 20 ppm. x and at least 1 μg / m based on the total volume of the flue gas stream. 3 and mercury vapor at a concentration of from about 0.5% per day relative to the total halogen in the device, wherein the release rate of the total halogen in the device does not exceed 0.5% per day.
Citation Information
Patent Citations
Method and system for removing mercury in exhaust gas
JP2004313833A
Activated carbon for removing mercury or mercury compound
JP2005349364A
Cylindrical activated carbon filter
JP2008284473A
Adsorbent and interior skin material for vehicle containing the same
JP2011092914A
Exhaust gas purification system and method using adsorbent polymer composites
JP2018507776A